Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
By using polymer X with a specific ratio, the flexibility and adhesion of the secondary battery electrode composite material layer is improved, and the problem of insufficient flexibility of the electrode composite material layer in the prior art is solved, and the output characteristics of the battery are improved.
Patent Information
- Application Number
- CN202380059872.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the softness of the secondary battery electrode composite material layer is insufficient, which affects the performance of the electrode.
A binder composition containing a specific polymer X is used, which contains more than 3% and less than 20% of the acid group-containing monomer units and more than 5% and less than 50% of the unsaturated monomer A.
The flexibility of the electrode composite material layer is significantly improved, the adhesion and dispersion of the electrode are enhanced, and the internal resistance of the secondary battery is reduced.
Smart Images

Figure BDA0005271958990000411 
Figure BDA0005271958990000421 
Figure BDA0005271958990000431
Abstract
Description
Technical Field
[0001] The present invention relates to a binder composition for a non-aqueous secondary battery electrode, a slurry composition for a non-aqueous secondary battery electrode, an electrode for a non-aqueous secondary battery, and a non-aqueous secondary battery. Background Art
[0002] Non-aqueous secondary batteries such as lithium-ion secondary batteries (hereinafter sometimes referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. Therefore, in recent years, with the goal of further improving the performance of secondary batteries, research is being conducted on the improvement of battery components such as electrodes.
[0003] Here, the electrode for secondary battery generally has an electrode composite material layer. Moreover, the electrode composite material layer is formed, for example, by dispersing an electrode active material and a non-aqueous secondary battery electrode binder composition containing a polymer that acts as a binder in a dispersion medium to form a slurry composition (non-aqueous secondary battery electrode slurry composition), applying the slurry composition on a current collector and drying it, thereby forming.
[0004] Therefore, in recent years, attempts have been made to improve the binder composition used to form the electrode composite material layer in order to further improve the performance of the secondary battery (see, for example, Patent Document 1).
[0005] For example, the following is reported in Patent Document 1: A binder composition comprising a water-soluble polymer having a weight average molecular weight of 50 to 95% by mass of structural units derived from ethylenically unsaturated carboxylic acid ester monomers and 5 to 50% by mass of structural units derived from ethylenically unsaturated carboxylate salt monomers, and having a binder composition that is capable of improving electrode formation, substrate adhesion, and flexibility without impairing the dispersibility and viscosity adjustment functions of an aqueous electrode composition.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: International Publication No. 2012 / 008539. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, in the above-mentioned conventional binder compositions, there is room for improvement in terms of enabling the electrode composite material layer to exhibit excellent flexibility.
[0011] Therefore, an object of the present invention is to provide a non-aqueous secondary battery electrode binder composition capable of allowing an electrode composite material layer to exhibit excellent flexibility.
[0012] Another object of the present invention is to provide a slurry composition for non-aqueous secondary battery electrodes that can allow an electrode composite material layer to exhibit excellent flexibility.
[0013] Furthermore, an object of the present invention is to provide an electrode for a non-aqueous secondary battery having an electrode composite material layer capable of exhibiting excellent flexibility.
[0014] Furthermore, an object of the present invention is to provide a non-aqueous secondary battery having the non-aqueous secondary battery electrode.
[0015] Solutions for solving problems
[0016] The present inventors conducted intensive research for the purpose of solving the above problems. Then, the present inventors found that if a binder composition containing a polymer X is used, and the polymer X contains an acidic group-containing monomer unit and a repeating unit derived from a specified unsaturated monomer in a specified ratio, an electrode composite material layer with excellent flexibility can be formed, thereby completing the present invention.
[0017] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is [1] a binder composition for non-aqueous secondary battery electrodes, comprising a polymer X, wherein the polymer X contains 3% by mass or more and 20% by mass or less of an acidic group-containing monomer unit, 5% by mass or more and Less than 50% by mass The unsaturated monomer A has a repeating unit derived from the unsaturated monomer A, wherein the solubility of the unsaturated monomer A in water is 1 g / 100 mL or more and 15 g / 100 mL or less, and the glass transition temperature of the unsaturated monomer A is 40° C. or less.
[0018] Thus, if the binder composition includes the polymer X, and the polymer X includes the acidic group-containing monomer unit and the repeating unit derived from the unsaturated monomer A in a predetermined ratio, the electrode composite material layer can exhibit excellent flexibility.
[0019] In the present invention, a polymer “containing a monomer unit” means that “a polymer obtained using the monomer contains a repeating unit derived from the monomer.” In this specification, “repeating units derived from unsaturated monomer A” may be referred to as “unsaturated monomer A units.”
[0020] In the present invention, the "content ratio (mass %)" of each monomer unit (repeating unit) contained in the polymer can be expressed as 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0021] Furthermore, in the present invention, "solubility in water" means solubility (dissolved amount) in 100 g of water at a temperature of 20°C.
[0022] In the present invention, the "glass transition temperature" of the unsaturated monomer A refers to the glass transition temperature (°C) obtained by measuring the homopolymer (i.e., homopolymer) of the unsaturated monomer A at a measuring temperature of -100°C to 180°C and a heating rate of 5°C / min using a differential scanning calorimeter (DSC7200 manufactured by SII Corporation) in accordance with JIS K7121. In addition, the weight average molecular weight of the homopolymer of the unsaturated monomer A is 10,000 or more and 1,000,000 or less.
[0023] [2] In the nonaqueous secondary battery electrode binder composition of [1], the polymer X may contain 20% by mass or less of repeating units derived from the unsaturated monomer A.
[0024] [3] In the nonaqueous secondary battery electrode binder composition of [1] or [2], the polymer X preferably contains 55% by mass or more and 90% by mass or less of a hydroxyl group-containing acrylic acid ester monomer unit.
[0025] When the polymer X further contains a hydroxyl group-containing acrylic acid ester monomer unit in the above-specified ratio, the adhesiveness and flexibility of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved.
[0026] [4] In the non-aqueous secondary battery electrode binder composition according to any one of [1] to [3] above, the weight average molecular weight of the polymer X is preferably 50,000 or more and less than 500,000.
[0027] When the weight average molecular weight (Mw) of the polymer X is within the above-specified range, the dispersibility of the slurry composition prepared using the binder composition can be improved, and the adhesiveness of the electrode composite material layer formed using the slurry composition can be improved.
[0028] In addition, in the present invention, the weight average molecular weight (Mw) can be measured using the method described in Examples of the present specification.
[0029] [5] In the nonaqueous secondary battery electrode binder composition according to any one of [1] to [5], the polymer X preferably contains 2% by mass or more and 30% by mass or less of a hydroxyl group-containing methacrylate monomer unit.
[0030] When the polymer X further contains a hydroxyl group-containing methacrylate monomer unit in the above-specified ratio, the adhesiveness and flexibility of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved.
[0031] [6] In the non-aqueous secondary battery electrode binder composition according to any one of [1] to [5] above, the unsaturated monomer A preferably contains at least one selected from the group consisting of 2-methoxyethyl acrylate, ethyl acrylate, methyl acrylate and vinyl acetate.
[0032] When the above-specified monomer is used as the unsaturated monomer A, the dispersibility of the slurry composition prepared using the binder composition can be further improved, and the adhesion and flexibility of the electrode composite material layer formed using the slurry composition can be improved.
[0033] [7] In the non-aqueous secondary battery electrode binder composition according to any one of [1] to [6], the polymer X preferably contains both or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate unit, and the total content of the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit in the polymer X is 30% by mass or more and 90% by mass or less.
[0034] When the above-specified polymer is used as polymer X, the dispersibility of the slurry composition prepared using the binder composition can be improved, and the adhesion and flexibility of the electrode composite material layer formed using the slurry composition can be improved, thereby improving the output characteristics of the obtained secondary battery.
[0035] [8] In the non-aqueous secondary battery electrode binder composition according to any one of [1] to [7], the polymer X preferably contains two or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate unit, and in the polymer X, the total content of the repeating units derived from the unsaturated monomer A, the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit is 80% by mass or more.
[0036] When the above-specified polymer is used as polymer X, the dispersibility of the slurry composition prepared using the binder composition can be improved, and the adhesion and flexibility of the electrode composite material layer formed using the slurry composition can be improved, thereby improving the output characteristics of the obtained secondary battery.
[0037] [9] In the nonaqueous secondary battery electrode binder composition according to any one of [1] to [8], the polymer X may contain 3% by mass or more and 20% by mass or less of a (meth)acrylamide monomer unit.
[0038] When the above-specified polymer is used as the polymer X, the adhesiveness and flexibility of the obtained electrode composite material layer can be improved. In addition, in this specification, "(meth)acrylamide" means acrylamide or methacrylamide.
[0039] In addition, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is
[10] a slurry composition for non-aqueous secondary battery electrodes, which comprises an electrode active material and the binder composition for non-aqueous secondary battery electrodes of any one of the above [1] to [9].
[0040] Thus, the non-aqueous secondary battery electrode slurry composition including any of the above-mentioned binder compositions can allow the electrode composite material layer to exhibit excellent flexibility.
[0041]
[11] The nonaqueous secondary battery electrode slurry composition of the above-mentioned
[10] preferably further contains a particulate polymer Y having a hydrophilic group.
[0042] When the nonaqueous secondary battery electrode slurry composition further contains a particulate polymer Y having a hydrophilic group, the dispersibility of the slurry composition and the adhesiveness and flexibility of an electrode composite material layer formed using the slurry composition can be improved.
[0043]
[12] In the non-aqueous secondary battery electrode slurry composition of
[11] , the content of the particulate polymer Y is preferably 0.1% by mass or more and 5% by mass or less, based on 100% by mass of the total solid content contained in the non-aqueous secondary battery electrode slurry composition.
[0044] When the content of the particulate polymer Y is within the above-specified range, the dispersibility of the slurry composition and the adhesiveness and flexibility of the electrode material layer formed using the slurry composition can be improved, and the internal resistance of the secondary battery can be reduced.
[0045]
[13] In the slurry composition for nonaqueous secondary battery electrodes according to any one of
[10] to
[12] , the electrode active material preferably contains olivine-type lithium iron phosphate.
[0046] When olivine-type lithium iron phosphate is used as an electrode active material, the stability of the secondary battery against overcharge can be improved.
[0047]
[14] The nonaqueous secondary battery electrode slurry composition according to any one of
[10] to
[13] above preferably further contains a conductive material containing carbon nanotubes.
[0048] If carbon nanotubes are used as a conductive material, the internal resistance of a non-aqueous secondary battery can be reduced.
[0049]
[15] In the nonaqueous secondary battery electrode slurry composition according to
[14] , it is preferred that the conductive material further contains a particulate conductive material.
[0050] If a particulate conductive material is further used as the conductive material, the flexibility of the electrode composite material layer formed using the slurry composition can be further improved.
[0051] In addition, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is
[16] a non-aqueous secondary battery electrode, which has an electrode composite material layer formed using the slurry composition for non-aqueous secondary battery electrodes described in any one of
[10] to
[15] .
[0052] The nonaqueous secondary battery electrode of the present invention is formed using any of the above-mentioned slurry compositions for nonaqueous secondary battery electrodes, and has an electrode composite material layer capable of exhibiting excellent flexibility.
[0053] Furthermore, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is
[17] a non-aqueous secondary battery comprising the electrode for a non-aqueous secondary battery of
[16] above.
[0054] A secondary battery having the nonaqueous secondary battery electrode has, for example, reduced internal resistance and excellent battery characteristics.
[0055] Effects of the Invention
[0056] According to the present invention, it is possible to provide a non-aqueous secondary battery electrode binder composition capable of allowing an electrode composite material layer to exhibit excellent flexibility.
[0057] Furthermore, according to the present invention, a slurry composition for non-aqueous secondary battery electrodes capable of allowing an electrode composite material layer to exhibit excellent flexibility can be provided.
[0058] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery electrode having an electrode composite material layer capable of exhibiting excellent flexibility.
[0059] Furthermore, according to the present invention, a nonaqueous secondary battery including the nonaqueous secondary battery electrode can be provided. DETAILED DESCRIPTION
[0060] Hereinafter, embodiments of the present invention will be described in detail.
[0061] Here, the binder composition for non-aqueous secondary battery electrodes of the present invention (hereinafter sometimes referred to as "binder composition") can be used when preparing a slurry composition for non-aqueous secondary battery electrodes (hereinafter sometimes referred to as "slurry composition"). Moreover, the slurry composition for non-aqueous secondary battery electrodes prepared using the binder composition for non-aqueous secondary battery electrodes of the present invention can be used when forming an electrode composite material layer possessed by an electrode (non-aqueous secondary battery electrode) of a non-aqueous secondary battery such as a lithium-ion secondary battery. Furthermore, the non-aqueous secondary battery of the present invention (hereinafter sometimes referred to as "secondary battery") is characterized in that a non-aqueous secondary battery electrode (hereinafter sometimes referred to as "electrode") having an electrode composite material layer formed by the slurry composition for non-aqueous secondary battery electrodes of the present invention is used.
[0062] (Binder composition for non-aqueous secondary battery electrodes)
[0063] The binder composition of the present invention is characterized by containing a predetermined polymer X. The binder composition of the present invention enables an electrode composite material layer formed using the binder composition to exhibit excellent flexibility.
[0064] As described above, the electrode composite material layer formed by the slurry composition prepared using the binder composition of the present invention has excellent flexibility, so when, for example, a secondary battery is manufactured, the electrode is wound, folded, etc. according to the shape of the secondary battery, the generation of cracks can be suppressed. Therefore, the electrode composite material layer formed by the slurry composition prepared using the binder composition of the present invention has a uniform structure and few cracks, so the internal resistance of the secondary battery can be reduced or the output characteristics can be improved.
[0065] In addition, even if the content of the binder composition of the present invention in the slurry composition (i.e., the content of the polymer X specified above) is small, the above-mentioned desired effect can be fully exerted. Therefore, the content of the binder composition of the present invention in the slurry composition (i.e., the content of the polymer X specified above) can be reduced, the internal resistance of the secondary battery can be reduced, and the flexibility of the formed electrode composite material layer can be fully improved.
[0066] In addition, the adhesive composition of the present invention may further optionally contain a solvent. In addition, the adhesive composition of the present invention may further optionally contain components (other components) other than the polymer X and the solvent.
[0067] <Polymer X>
[0068] The polymer X is a component that can function as a dispersant for dispersing components such as electrode active materials and conductive materials well in a slurry composition prepared using the binder composition. In addition, the polymer X can also function as a binder in an electrode composite material layer formed using the slurry composition.
[0069] The polymer X contains an acidic group-containing monomer unit and a repeating unit derived from a specified unsaturated monomer A (i.e., an unsaturated monomer A unit). Here, the solubility of the unsaturated monomer A in water is within a specified range, and the glass transition temperature is below a specified value. Moreover, the content ratio of the acidic group-containing monomer unit and the content ratio of the unsaturated monomer A unit in the polymer X are respectively within a specified range.
[0070] In addition, polymer X may contain at least one of hydroxyl-containing acrylate monomer units, hydroxyl-containing methacrylate monomer units and (meth) acrylamide monomer units in addition to the above-mentioned acidic group-containing monomer units and unsaturated monomer A units. Specifically, polymer X may contain at least one of hydroxyl-containing acrylate monomer units and hydroxyl-containing methacrylate monomer units in addition to the above-mentioned acidic group-containing monomer units and unsaturated monomer A units. Alternatively, polymer X may contain at least one of hydroxyl-containing acrylate monomer units and hydroxyl-containing methacrylate units in addition to the above-mentioned acidic group-containing monomer units and unsaturated monomer A units. Furthermore, polymer X may contain at least one of hydroxyl-containing acrylate monomer units, hydroxyl-containing methacrylate monomer units and (meth) acrylamide monomer units in addition to the above-mentioned acidic group-containing monomer units and unsaturated monomer A units.
[0071] Furthermore, the polymer X may contain monomer units other than the above-mentioned acidic group-containing monomer units, unsaturated monomer A units, hydroxyl-containing acrylate monomer units, hydroxyl-containing methacrylate monomer units and (meth)acrylamide monomer units (hereinafter sometimes referred to as "other monomer units") within the range that the desired effect of the present invention can be obtained. Of course, the polymer X may not contain other monomer units.
[0072] In addition, the polymer X is not particularly limited, and is usually a water-soluble polymer. In the present invention, the polymer is "water-soluble" when 0.5 g (solid content conversion) of the polymer is dissolved in 100 g of water at 25°C, and the insoluble content is less than 5.0% by mass.
[0073] <<Acidic group-containing monomer unit>>
[0074] Examples of the acidic group-containing monomer capable of forming the acidic group-containing monomer unit in the polymer X include carboxylic acid group-containing monomers, sulfonic acid group-containing monomers, and phosphoric acid group-containing monomers.
[0075] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.
[0076] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.
[0077] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid.
[0078] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.
[0079] Examples of the dicarboxylic acid derivatives include maleic acid esters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, methylallyl maleate, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.
[0080] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0081] Furthermore, as the monomer having a carboxylic acid group, an acid anhydride that generates a carboxyl group by hydrolysis can also be used.
[0082] In addition, monoesters and diesters of α,β-ethylenically unsaturated polycarboxylic acids such as monoethyl maleate, diethyl maleate, monobutyl maleate, dibutyl maleate, monoethyl fumarate, diethyl fumarate, monobutyl fumarate, dibutyl fumarate, monocyclohexyl fumarate, dicyclohexyl fumarate, monoethyl itaconate, diethyl itaconate, monobutyl itaconate, and dibutyl itaconate can also be mentioned.
[0083] In addition, in the carboxylic acid group of the carboxylic acid group-containing monomer, the hydrogen atom may be substituted by an inorganic ion or an organic ion to form an inorganic salt or an organic salt. That is, the carboxylic acid group-containing monomer may be in the form of a carboxylate salt.
[0084] Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0085] In addition, the hydrogen atom in the sulfonic acid group in the sulfonic acid group-containing monomer may be replaced by an inorganic ion or an organic ion to form an inorganic salt or an organic salt. That is, the sulfonic acid group-containing monomer may be in the form of a sulfonate.
[0086] Examples of the phosphoric acid group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0087] In addition, in the phosphoric acid group in the phosphoric acid group-containing monomer, the hydrogen atom may be replaced by an inorganic ion or an organic ion to form an inorganic salt or an organic salt. That is, the phosphoric acid group-containing monomer may be in the form of a phosphate.
[0088] In addition, these acidic group-containing monomers may be used alone or in combination of two or more at any ratio.
[0089] Furthermore, from the viewpoint of further improving the adhesiveness of the formed electrode composite material layer, as the acidic group-containing monomer, a carboxylic acid group-containing monomer or a sulfonic acid group-containing monomer is preferably used, a carboxylic acid group-containing monomer is more preferably used, and acrylic acid is further preferably used.
[0090] The content ratio of the acidic group-containing monomer unit in the polymer X, when all the monomer units (all repeating units) contained in the polymer X are taken as 100 mass %, needs to be 3 mass % or more, preferably 4.5 mass % or more, more preferably 5 mass % or more, further preferably 6 mass % or more, and may be 7 mass % or more, and needs to be 20 mass % or less, preferably 17.5 mass % or less, and more preferably 15 mass % or less.
[0091] If the content ratio of the acidic group-containing monomer unit in polymer X is more than 3% by mass, it is speculated that the interaction between polymer X and the electrode active material is improved, so the dispersibility of the slurry composition prepared using the binder composition can be improved. On the other hand, if the content ratio of the acidic group-containing monomer unit in polymer X is less than 20% by mass, it is speculated that the flexibility of the molecular chain of polymer X is improved, so the adhesion and flexibility of the electrode composite material layer formed using the slurry composition can be improved. In addition, if the content ratio of the acidic group-containing monomer unit in polymer X is less than 20% by mass, it is speculated that the electrostatic repulsion of polymer X is reduced, and the adsorption of the electrode active material is improved, so the dispersibility of the slurry composition can be further improved.
[0092] <<Unsaturated monomer A unit>>
[0093] The unsaturated monomer A unit is a repeating unit derived from the unsaturated monomer A.
[0094] The unsaturated monomer A unit in the polymer X can impart adhesiveness and flexibility to the electrode composite material layer formed using the slurry composition including the binder composition.
[0095] Here, the solubility of the unsaturated monomer A capable of forming the unsaturated monomer A unit in water needs to be 1 g / 100 mL or more, more preferably 1.2 g / 100 mL or more, further preferably 1.5 g / 100 mL or more, and further preferably 2 g / 100 mL or more, and needs to be 15 g / 100 mL or less, preferably 13 g / 100 mL or less, and more preferably 12 g / 100 mL or less.
[0096] If the solubility of the unsaturated monomer A in water is 1g / 100mL or more, the solubility of the polymer X in water can be suppressed from decreasing, ensuring that the dispersibility of the slurry composition prepared using the binder composition is sufficiently high. In addition, if the solubility of the unsaturated monomer A in water is 1g / 100mL or more, it is possible to ensure that the polymerizability of the unsaturated monomer A when preparing the polymer X is sufficiently high. On the other hand, if the solubility of the unsaturated monomer A in water is 15g / 100mL or less, it is presumed that the affinity of the polymer X to the electrode active material is improved, and therefore the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved.
[0097] Furthermore, the glass transition temperature of the unsaturated monomer A which can form the unsaturated monomer A unit needs to be 40° C. or lower, preferably 30° C. or lower, more preferably 10° C. or lower, and further preferably 0° C. or lower.
[0098] If the glass transition temperature of the unsaturated monomer A is 40° C. or lower, it is presumed that the flexibility of the polymer X is improved, and thus the adhesion and flexibility of the electrode composite material layer formed using the slurry composition containing the binder composition can be sufficiently improved.
[0099] The lower limit of the glass transition temperature of the unsaturated monomer A is not particularly limited, but is preferably -60°C or higher, and preferably -55°C or higher, for example.
[0100] The unsaturated monomer A that can form the unsaturated monomer A unit is not particularly limited as long as it has an ethylenically unsaturated bond, has a solubility in water within the above-specified range, and has a glass transition temperature of the above-specified value or less.
[0101] Examples of the unsaturated monomer A include 2-methoxyethyl acrylate (also referred to as "2-methoxyethyl acrylate". Solubility in water: 11.6 g / 100 mL, glass transition temperature: -50°C), ethyl acrylate (solubility in water: 1.5 g / 100 mL, glass transition temperature: -22°C), methyl acrylate (solubility in water: 6 g / 100 mL, glass transition temperature: 3°C) and vinyl acetate (solubility in water: 2.5 g / 100 mL, glass transition temperature: 32°C).
[0102] These may be used alone or in combination of two or more at any ratio.
[0103] Among them, as the unsaturated monomer A, 2-methoxyethyl acrylate, ethyl acrylate and methyl acrylate are preferably used, and 2-methoxyethyl acrylate is particularly preferably used.
[0104] The content ratio of the unsaturated monomer A unit in the polymer X needs to be 5% by mass or more, preferably 6% by mass or more, more preferably 7% by mass or more, and can be 25% by mass or more, or 27.5% by mass or more, or 30% by mass or more, and needs to be less than 50% by mass, preferably 47% by mass or less, more preferably 42% by mass or less, and can be 20% by mass or less, or 17.5% by mass or less, or 15% by mass or less, when all monomer units (all repeating units) contained in the polymer X are taken as 100% by mass.
[0105] If the content ratio of the unsaturated monomer A in the polymer X is 5% by mass or more, the adhesion and flexibility of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved. On the other hand, if the content ratio of the unsaturated monomer A in the polymer X is less than 50% by mass, the solubility of the polymer X in water can be suppressed from decreasing, thereby improving the dispersibility of the slurry composition prepared using the binder composition.
[0106] In particular, when the content ratio of the unsaturated monomer A unit in the polymer X is 25 mass % or more and 50 mass % or less, the dispersibility of the obtained slurry composition can be further improved, thereby improving the output characteristics of the obtained secondary battery.
[0107] <<Hydroxy-containing acrylate monomer unit>>
[0108] The polymer X preferably further contains hydroxyl-containing acrylate monomer units.
[0109] If the polymer X further contains a hydroxyl-containing acrylate monomer unit, it is speculated that the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved due to the interaction of hydroxyl groups between the molecules of the polymer X. In addition, if the polymer X further contains a hydroxyl-containing acrylate monomer unit, it is speculated that the flexibility of the molecular chain of the polymer X is further improved, so the flexibility of the electrode composite material layer can be further improved.
[0110] Examples of the hydroxyl-containing acrylate monomers that can form the hydroxyl-containing acrylate monomer units in the polymer X include: alkyl acrylates such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate (also referred to as "hydroxyalkyl acrylate monomers"); general formula: CH2=CH-COO-(C q H 2q O) p -H (wherein p is an integer of 2 to 9, and q is an integer of 2 to 4) and esters of acrylic acid (also referred to as "polyalkylene glycol acrylate monomers"), etc. These may be used alone or in any combination.
[0111] Among them, from the viewpoint of improving the adhesion and flexibility of the electrode composite material layer, as the hydroxyl-containing acrylate monomer, it is preferred to use acrylic acid alkanol esters (hydroxyalkyl acrylate monomers) such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate.
[0112] The content ratio of the hydroxyl-containing acrylate monomer unit in the polymer X is preferably 55% by mass or more, more preferably 57.5% by mass or more, further preferably 60% by mass or more, more preferably 65% by mass or more, preferably 90% by mass or less, preferably 85% by mass or less, and more preferably 80% by mass or less, when all monomer units (all repeating units) contained in the polymer X are taken as 100% by mass.
[0113] If the content ratio of the hydroxyl-containing acrylate monomer unit in polymer X is above the above lower limit, it is inferred that the interaction between the hydroxyl groups of the molecules of polymer X is increased, so the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved. In addition, if the content ratio of the hydroxyl-containing acrylate monomer unit in polymer X is above the above lower limit, it is inferred that the flexibility of the molecular chain of polymer X is further improved, so the flexibility of the electrode composite material layer can be fully improved. On the other hand, if the content ratio of the hydroxyl-containing acrylate monomer unit in polymer X is below the above upper limit, the flexibility of the molecular chain of polymer X can be avoided from being excessively increased, thereby improving the adhesion of the electrode composite material layer.
[0114] <<Hydroxy-containing methacrylate monomer unit>>
[0115] The polymer X preferably further contains hydroxyl-containing methacrylate monomer units.
[0116] If the polymer X further contains a hydroxyl-containing methacrylate monomer unit, it is presumed that the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved due to the interaction of the hydroxyl groups between the molecules of the polymer X. In addition, if the polymer X further contains a hydroxyl-containing methacrylate monomer unit, it is presumed that the three-dimensional structure of the polymer X is expanded due to the steric hindrance of the molecular chain of the polymer X, so that the polymer X can be thinly and widely coated on the surface of the electrode active material, thereby further improving the flexibility of the electrode composite material layer.
[0117] Examples of the hydroxyl-containing methacrylate monomers that can form the hydroxyl-containing methacrylate monomer units in the polymer X include alkanol methacrylates such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate (also referred to as "hydroxyalkyl methacrylate monomers"); general formula: CH2=C(CH3)-COO-(C s H 2s O) r -H (wherein r represents an integer of 2 to 9, and s represents an integer of 2 to 4) and esters of methacrylic acid (also referred to as "methacrylic acid polyalkylene glycol ester monomer"), etc. These may be used alone or in combination of two or more at any ratio.
[0118] Among them, from the viewpoint of further improving the adhesion and flexibility of the electrode composite material layer, as the hydroxyl-containing methacrylate monomer, it is preferred to use alkanol methacrylic acid esters (hydroxyalkyl methacrylate monomers) such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate.
[0119] The content ratio of the hydroxyl-containing methacrylate monomer unit in the polymer X is preferably 2% by mass or less, more preferably 5% by mass or more, further preferably 6% by mass or more, further preferably 7% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, when all monomer units (all repeating units) contained in the polymer X are taken as 100% by mass.
[0120] When the content ratio of the hydroxyl group-containing methacrylate monomer unit in the polymer X is within the above-specified range, the adhesiveness and flexibility of the electrode composite material layer formed using the slurry composition containing the binder composition can be further improved.
[0121] The content of the hydroxyl group-containing methacrylate monomer units in the polymer X may be 0% by mass or more, or 10% by mass or less, when all monomer units (all repeating units) contained in the polymer X are taken as 100% by mass.
[0122] <<Total content of hydroxyl-containing acrylate monomer units and hydroxyl-containing methacrylate units>>
[0123] In the case where the polymer X includes two or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate unit, the total content ratio of the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit in the polymer X is preferably 30% by mass or more, more preferably 35% by mass or more, further preferably 40% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, 60% by mass or less, 57.5% by mass or less, or 55% by mass or less. If the total content ratio of the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit in the polymer X is above the above lower limit, it is inferred that the affinity of the polymer X to the electrode active material is improved, so the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be improved. In addition, if the total content ratio of the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate units in the polymer X is above the above lower limit, the dispersibility of the slurry composition prepared using the binder composition can be further improved. Furthermore, if the total content ratio of the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate units in the polymer X is below the above upper limit, the flexibility of the molecular chain of the polymer X can be avoided from being excessively increased, and the adhesion of the electrode composite material layer can be improved.
[0124] <<Total content of repeating units derived from unsaturated monomer A, hydroxyl-containing acrylate monomer units, and the above-mentioned hydroxyl-containing methacrylate units>>
[0125] In the case where the polymer X includes two or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate unit, in the polymer X, the total content ratio of the repeating unit from the unsaturated monomer A, the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit is preferably 80% by mass or more, more preferably 84% by mass or more, preferably 97% by mass or less, and more preferably 93% by mass or less when all monomer units (all repeating units) contained in the polymer X are taken as 100% by mass. If the total content ratio of the repeating unit from the unsaturated monomer A, the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit in the polymer X is above the above lower limit, the dispersibility of the slurry composition prepared using the binder composition can be improved, and the adhesion and flexibility of the electrode composite material layer formed using the slurry composition can be improved, and the output characteristics of the secondary battery obtained can be improved. If the total content of the repeating units derived from the unsaturated monomer A, the hydroxyl-containing acrylate monomer units and the hydroxyl-containing methacrylate units in the polymer X is below the upper limit, the adhesiveness of the obtained electrode composite material layer can be improved, and the output characteristics of the obtained secondary battery can be improved.
[0126] <<(Meth)acrylamide monomer unit>>
[0127] The polymer X may further contain a (meth)acrylamide monomer unit. If the polymer X further contains a (meth)acrylamide monomer unit, the adhesiveness and flexibility of the obtained electrode composite material layer can be improved.
[0128] As the (meth) acrylamide monomer unit that can form the (meth) acrylamide monomer unit in polymer X, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, N-hydroxyethyl acrylamide, N-hydroxyethyl methacrylamide, etc. can be cited. In addition, these can be used alone or in any ratio. Two or more. Among them, from the viewpoint of improving the adhesion and flexibility of the obtained electrode composite material layer, acrylamide and N-hydroxyethyl acrylamide are preferred. In addition, for the unit that can belong to other monomer units recorded in this specification, even if there is a (meth) acrylamide group, it does not belong to "(meth) acrylamide monomer unit".
[0129] The content ratio of the (methyl) acrylamide monomeric unit in polymer X is preferably 3% by mass or more, more preferably 4.5% by mass or more, more preferably 7.5% by mass or more, preferably 20% by mass or less, more preferably 18% by mass or less, and more preferably 16% by mass or less, when all monomeric units (all repeating units) contained in polymer X are taken as 100% by mass. If the content ratio of the (methyl) acrylamide monomeric unit in polymer X is above the above lower limit, the adhesion of the obtained electrode composite material layer can be improved. In addition, if the content ratio of the (methyl) acrylamide monomeric unit in polymer X is below the above upper limit, it is inferred that it is because polymer X can be suppressed from becoming too hard, so the adhesion and flexibility of the obtained electrode composite material layer can be improved. Thus, the output characteristics of the obtained secondary battery can be improved.
[0130] <<Method for preparing polymer X>>
[0131] The polymer X is not particularly limited and can be prepared, for example, as follows.
[0132] The above-mentioned acidic group-containing monomer and unsaturated monomer A, as well as hydroxyl-containing acrylate monomers and hydroxyl-containing methacrylate monomers that can be used arbitrarily are mixed in a solvent such as water. In addition, the acidic group-containing monomer can be arbitrarily dissolved in an alkaline aqueous solution and further neutralized to prepare an aqueous solution, and then mixed with unsaturated monomer A and other monomers that can be arbitrarily matched. A polymerization accelerator is added to the obtained mixture. After that, a polymerization initiator is added to initiate the polymerization reaction. After that, as needed, one or more polymerization accelerators, polymerization initiators, and polymerization cycles can also be performed. When the polymerization initiator is added to initiate the polymerization reaction, the polymerization temperature is preferably, for example, 35°C or more and 65°C or less, and more preferably 40°C or more and 55°C or less. In addition, the time of the polymerization reaction between the addition of the polymerization initiator and the addition of the polymerization accelerator is, for example, preferably 5 minutes or more and 40 minutes or less, and more preferably 10 minutes or more and 30 minutes or less. In addition, the above operation is preferably performed under a nitrogen environment. In addition, a chain transfer agent can also be used as a polymerization aid when performing the polymerization reaction. After the polymerization reaction, a reaction terminator is used to terminate the polymerization reaction. Then, after the product is cooled and placed in an air environment, a lithium hydroxide aqueous solution or the like is added to adjust the pH of the product to 7.0 or more and 9.0 or less.
[0133] The polymerization initiator is not particularly limited, and known polymerization initiators can be used. Examples of the polymerization initiator include potassium persulfate, sodium persulfate, ammonium persulfate, etc. Potassium persulfate is particularly preferred. When the polymerization initiator is added multiple times, the polymerization initiators each time may be the same or different.
[0134] The amount of the polymerization initiator used can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.
[0135] As the polymerization accelerator, for example, L-ascorbic acid, sodium bisulfite, etc. can be mentioned. In the case of adding the polymerization accelerator multiple times, the polymerization accelerators each time can be the same or different. In particular, when initiating the polymerization reaction, it is preferred that L-ascorbic acid exists as a polymerization accelerator in the polymerization system.
[0136] The amount of the polymerization accelerator used can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.
[0137] <<Weight average molecular weight (Mw)>>
[0138] The weight average molecular weight (Mw) of polymer X is preferably 50,000 or more, more preferably 75,000 or more, further preferably 100,000 or more, preferably less than 2,000,000, more preferably less than 1,500,000, further preferably less than 1,000,000, and may be less than 500,000, less than 400,000, or less than 300,000.
[0139] If the weight average molecular weight (Mw) of polymer X is above the above lower limit, the adhesion of the electrode composite material layer formed using the slurry composition containing the binder composition can be further improved. On the other hand, if the weight average molecular weight (Mw) of polymer X is less than the above upper limit, the dispersibility of the slurry composition prepared using the binder composition can be further improved.
[0140] The weight average molecular weight (Mw) of the polymer X can be controlled by the polymerization conditions in the method for preparing the polymer X, specifically, by the type and amount of the polymerization initiator, polymerization accelerator, chain transfer agent, etc., and the time and temperature of the polymerization reaction.
[0141] <<Molecular weight distribution (Mw / Mn)>>
[0142] The molecular weight distribution (Mw / Mn) of the polymer X is preferably 1.5 or more, more preferably 1.8 or more, and even more preferably 2.2 or more, and is preferably 10 or less, more preferably 7 or less, and even more preferably 4 or less.
[0143] The molecular weight distribution (Mw / Mn) of polymer X can be controlled by the polymerization conditions in the method for preparing polymer X, specifically, by the type and amount of polymerization initiator, polymerization accelerator, chain transfer agent, etc., and the time and temperature of the polymerization reaction.
[0144] In the present invention, the molecular weight distribution (Mw / Mn) can be measured using the method described in Examples of the present specification.
[0145] <Solvent>
[0146] As the solvent that can be used to prepare the binder composition of the present invention, a known solvent that can dissolve or disperse the above-mentioned polymer X can be used. Among them, as the solvent, water is preferably used. In addition, as at least a part of the solvent included in the binder composition, a solvent such as water used in preparing polymer X can be used.
[0147] <Other ingredients>
[0148] In addition, the adhesive composition of the present invention may also include any other components such as reinforcing materials, leveling agents, viscosity modifiers, electrolyte additives, etc. in addition to the above-mentioned polymer X and solvent. These are not particularly limited as long as they do not affect the battery reaction, and known components can be used. In addition, these components can be used alone or in combination of two or more in any ratio.
[0149] Furthermore, the binder composition of the present invention may further contain the particulate polymer Y which can be contained in the slurry composition of the present invention described later.
[0150] <Method for preparing adhesive composition>
[0151] The adhesive composition of the present invention can be prepared by, for example, mixing the polymer X and other components in a solvent such as water by a known method.
[0152] Furthermore, for example, an aqueous solution or aqueous dispersion of the polymer X obtained by the above-mentioned method for producing the polymer X can also be used as it is as the adhesive composition of the present invention.
[0153] Furthermore, for example, after mixing the polymer X with the electrode active material, other components such as the granular polymer Y which may be used arbitrarily may be added, thereby simultaneously preparing the binder composition and the slurry composition described below.
[0154] (Slurry composition for non-aqueous secondary battery electrodes)
[0155] The slurry composition of the present invention is characterized by comprising an electrode active material and the above-mentioned binder composition.
[0156] Since the slurry composition of the present invention includes the binder composition of the present invention, it has excellent dispersibility, and the electrode composite material layer formed using the slurry composition can exhibit excellent adhesion and flexibility.
[0157] Moreover, the dispersibility of the slurry composition of the present invention is excellent, so it is possible to form an electrode composite material layer with a uniform structure. And then, as described above, the flexibility of the electrode composite material layer formed by the slurry composition of the present invention is also excellent, so when, for example, a secondary battery is manufactured, the electrode is wound, folded, etc. according to the shape of the secondary battery, The generation of cracks can be suppressed. Therefore, the electrode composite material layer formed by the slurry composition of the present invention has a uniform structure, and there are few cracks, so the internal resistance of the secondary battery can be reduced.
[0158] Furthermore, the slurry composition of the present invention may optionally contain a particulate polymer Y and a conductive material in addition to the electrode active material and the binder composition.
[0159] Furthermore, the slurry composition of the present invention usually further contains a dispersion medium such as water.
[0160] Furthermore, the slurry composition of the present invention may further contain components (other components) other than the above-mentioned electrode active material, binder composition, particulate polymer, conductive material and dispersion medium.
[0161] The content ratio of the electrode active material in the slurry composition is preferably 90% by mass or more and 99% by mass or more, for example, when the total solid content contained in the slurry composition is taken as 100% by mass. If the content ratio of the electrode active material in the slurry composition is above the above lower limit, the energy density of the secondary battery can be improved. On the other hand, if the content ratio of the electrode active material in the slurry composition is below the above upper limit, it is possible to ensure that the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite material layer are sufficiently high.
[0162] The slurry composition of the present invention may be a non-aqueous secondary battery positive electrode slurry composition containing a positive electrode active material as an electrode active material, or may be a non-aqueous secondary battery negative electrode slurry composition containing a negative electrode active material as an electrode active material. Here, in the positive electrode composite material layer, flexibility may be a problem, so from the viewpoint of further improving the flexibility of the positive electrode composite material layer formed as the electrode composite material layer, the slurry composition of the present invention is preferably a non-aqueous secondary battery positive electrode slurry composition.
[0163] Hereinafter, a case where the nonaqueous secondary battery electrode slurry composition of the present invention is a lithium ion secondary battery positive electrode slurry composition will be described in detail, but the present invention is not limited to the following example.
[0164] <Electrode active material (positive electrode active material)>
[0165] Here, the positive electrode active material of the lithium ion secondary battery is not particularly limited, and a known positive electrode active material can be used.
[0166] Specifically, as the positive electrode active material, a compound containing a transition metal can be used, such as a transition metal oxide, a transition metal sulfide, a composite metal oxide of lithium and a transition metal, etc. In addition, as the transition metal, for example, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, etc. can be cited.
[0167] Here, examples of transition metal oxides include MnO, MnO2, V2O5, V6O 13 , TiO2, Cu2V2O3, amorphous V2O-P2O5, amorphous MoO3, amorphous V2O5, amorphous V6O 13 wait.
[0168] Examples of transition metal sulfides include TiS2, TiS3, amorphous MoS2, and FeS.
[0169] Examples of the composite metal oxide of lithium and a transition metal include a lithium-containing composite metal oxide having a layered structure, a lithium-containing composite metal oxide having a spinel structure, and a lithium-containing composite metal oxide having an olivine structure.
[0170] Examples of lithium-containing composite metal oxides having a layered structure include lithium-containing cobalt oxide (LiCoO2), lithium-containing nickel oxide (LiNiO2), Co-Ni-Mn lithium-containing composite oxide (Li(CoMnNi)O2), Ni-Mn-Al lithium-containing composite oxide, Ni-Co-Al lithium-containing composite oxide, and a solid solution of LiMaO2 and Li2MbO3. In addition, examples of Co-Ni-Mn lithium-containing composite oxides include Li[Ni 0.5 Co 0.2 Mn 0.3 ]O2, Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, etc. In addition, as a solid solution of LiMaO2 and Li2MbO3, for example, xLiMaO2·(1-x)Li2MbO3, etc. can be cited. Here, x represents a number satisfying 0<x<1, Ma represents one or more transition metals with an average oxidation state of 3+, and Mb represents one or more transition metals with an average oxidation state of 4+. As such a solid solution, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 ]O2, etc.
[0171] In this specification, the term "average oxidation state" refers to the average oxidation state of the above-mentioned "one or more transition metals", which is calculated from the molar amount and valence of the transition metals. For example, when "one or more transition metals" are 50 mol% Ni 2+ and 50 mol% Mn 4+ In the case of the above-mentioned structure, the average oxidation state of "one or more transition metals" is (0.5)×(2+)+(0.5)×(4+)=3+.
[0172] As lithium-containing composite metal oxides having a spinel structure, for example, lithium manganate (LiMn2O4) and compounds in which a portion of Mn in lithium manganate (LiMn2O4) is replaced by other transition metals can be cited. As specific examples, LiNi 0.5 Mn 1.5 O4 etc.Li s [Mn 2-t Mc t ]O4. Here, Mc represents one or more transition metals with an average oxidation state of 4+. Specific examples of Mc include Ni, Co, Fe, Cu, Cr, etc. In addition, t represents a number satisfying 0<t<1, and s represents a number satisfying 0≤s≤1. In addition, Li can also be used as a positive electrode active material. 1+x Mn 2-x A lithium-excess spinel compound represented by O4 (0<X<2), etc.
[0173] Examples of lithium-containing composite metal oxides having an olivine structure include olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), and olivine-type lithium manganese iron phosphate (LiMn 1-x Fe x PO4; 0<x<1) etc. y An olivine-type lithium phosphate compound represented by MdPO4. Here, Md represents one or more transition metals with an average oxidation state of 3+, such as Mn, Fe, Co, etc. In addition, y represents a number satisfying 0≤y≤2. Furthermore, Li y The Md of the olivine-type lithium phosphate compound represented by MdPO4 may be partially substituted by other metals. Examples of the metals that can be substituted include Cu, Mg, Zn, V, Ca, Sr, Ba, Ti, Al, Si, B, and Mo.
[0174] Among these, olivine-type lithium iron phosphate is preferably used from the viewpoint of improving the stability of the secondary battery against overcharge.
[0175] Here, as the olivine-type lithium iron phosphate, carbon-coated olivine-type lithium iron phosphate particles in which at least a part of the surface of the olivine-type lithium iron phosphate particles is coated with a carbon coating layer may be used.
[0176] In addition, the particle size of the positive electrode active material is not particularly limited, and can be appropriately adjusted within the range of the desired effect of the present invention. For example, the average particle size of the positive electrode active material is preferably less than 2 μm. In the present invention, the average particle size of the positive electrode active material refers to the particle size D50 at which the cumulative volume calculated from the small diameter side becomes 50% in the particle size distribution (volume basis) measured using a laser diffraction particle size measuring device made by Malvern.
[0177] <Adhesive composition>
[0178] As the adhesive composition, the above-mentioned adhesive composition of the present invention can be used.
[0179] The addition amount of the binder composition when preparing the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention. For example, when the total solid content contained in the slurry composition is taken as 100% by mass, the addition amount of the binder composition can be adjusted so that the content ratio of polymer X is more than 0.1% by mass and less than 5% by mass, preferably more than 0.1% by mass and less than 3% by mass, more preferably more than 0.1% by mass and less than 1% by mass. If the content ratio of polymer X in the slurry composition is more than the above lower limit, the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite material layer can be further improved. On the other hand, if the content ratio of polymer X in the slurry composition is less than the above upper limit, the internal resistance of the secondary battery can be reduced.
[0180] <Granular polymer Y>
[0181] The particulate polymer Y is a component that can function as a binder in the electrode composite material layer together with the polymer X.
[0182] In addition, the particulate polymer Y is a polymer different from the polymer X described above.
[0183] Here, the particulate polymer Y is usually water-insoluble. In the present invention, the polymer being "water-insoluble" means that when 0.5 g (in terms of solid content) of the polymer is dissolved in 100 g of water at 25°C, the amount of insoluble components is 90% by mass or more.
[0184] Furthermore, the particulate polymer Y preferably contains a hydrophilic group. If a particulate polymer containing a hydrophilic group (a particulate polymer containing a hydrophilic group) is used as the particulate polymer Y, the dispersibility of the slurry composition and the adhesiveness and softness of the formed electrode composite material layer can be further improved.
[0185] Here, the method for introducing the hydrophilic group into the particulate polymer Y is not particularly limited, and for example, a method of using a hydrophilic group-containing monomer when polymerizing the particulate polymer Y to form a hydrophilic group-containing monomer unit in the obtained particulate polymer Y can be adopted.
[0186] <<Hydrophilic group-containing monomer unit>>
[0187] Examples of the hydrophilic group-containing monomer capable of forming the hydrophilic group-containing monomer unit in the particulate polymer Y include acidic group-containing monomers such as carboxylic acid group-containing monomers, sulfonic acid group-containing monomers and phosphoric acid group-containing monomers; and hydroxyl group-containing monomers.
[0188] As the acidic group-containing monomer (a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphoric acid group-containing monomer, etc.), various acidic group-containing monomers that can be used for preparing the above-mentioned polymer X can be used.
[0189] Examples of the hydroxyl-containing monomer include alkanol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate (2-hydroxyethyl acrylate), 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; general formula: CH2=CR 1 -COO-(C q H 2q O) p -H (wherein p represents an integer of 2 to 9, q represents an integer of 2 to 4, R 1Esters of polyalkylene glycol represented by alkylene glycol (representing hydrogen or methyl) and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2′-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2′-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl-6-hydroxyhexyl ethers; polyoxyalkylene glycol mono(meth)allyl ethers such as diethylene glycol mono(meth)allyl ether and dipropylene glycol mono(meth)allyl ether; mono(meth)allyl ethers of halogen and hydroxyl substituents of (poly)alkylene glycols such as glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyphenols such as eugenol and isoeugenol and their halogen substituents; (meth)allyl sulfides of alkylene glycols such as (meth)allyl-2-hydroxyethyl sulfide and (meth)allyl-2-hydroxypropyl sulfide, etc.
[0190] In the present invention, "(meth)allyl" means an allyl group and / or a methallyl group, and "(meth)acryloyl" means an acryloyl group and / or a methacryloyl group.
[0191] As the hydrophilic group-containing monomer, one kind may be used alone, or two or more kinds may be used in combination at any ratio.
[0192] Moreover, as the hydrophilic group-containing monomer, from the viewpoint of further improving the dispersibility of the slurry composition and the adhesion of the formed electrode composite material layer, it is preferred to use an acidic group-containing monomer (a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer and a phosphoric acid group-containing monomer, etc.), and from the viewpoint of further improving the adhesion of the formed electrode composite material layer, it is more preferred to use an acidic group-containing monomer and a hydroxyl group-containing monomer in combination, and it is further preferred to use a carboxylic acid group-containing monomer and a hydroxyl group-containing monomer in combination.
[0193] -Content ratio-
[0194] The content of the hydrophilic group-containing monomeric unit in the granular polymer Y is preferably 1% by mass or more and 10% by mass or less, based on 100% by mass of all monomeric units contained in the granular polymer Y. If the content of the hydrophilic group-containing monomeric unit in the granular polymer Y is within the above-specified range, the dispersibility of the slurry composition and the adhesion and softness of the formed electrode composite material layer can be further improved.
[0195] Furthermore, in the case where the granular polymer Y includes both acidic group-containing monomer units (carboxyl-containing monomer units, sulfonic acid-containing monomer units, and phosphoric acid-containing monomer units, etc.) and hydroxyl-containing monomer units as hydrophilic group-containing monomer units, the proportion of the hydrophilic group-containing monomer units in the granular polymer Y (i.e., the total proportion of the acidic group-containing monomer units and the hydroxyl-containing monomer units) is more preferably 2% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or less, and more preferably 4% by mass or less, when all monomer units contained in the granular polymer Y are taken as 100% by mass. If the total proportion of the acidic group-containing monomer units and the hydroxyl-containing monomer units in the granular polymer Y is within the above-defined range, the dispersibility of the slurry composition and the adhesion and softness of the formed electrode composite material layer can be further improved.
[0196] In addition, in the case where the granular polymer Y includes an acidic group-containing monomer unit (a carboxylic acid group-containing monomer unit, a sulfonic acid group-containing monomer unit and a phosphoric acid group-containing monomer unit, etc.) as a hydrophilic group-containing monomer unit, the content ratio of the acidic group-containing monomer unit in the granular polymer Y is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 1.5% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and more preferably 2.5% by mass or less. If the content ratio of the acidic group-containing monomer unit in the granular polymer Y is above the above lower limit, the dispersibility of the slurry composition and the adhesion of the electrode composite material layer formed can be further improved. On the other hand, if the content ratio of the acidic group-containing monomer unit in the granular polymer Y is below the above upper limit, the softness of the electrode composite material layer formed can be ensured to be sufficiently high.
[0197] In addition, in the case where the granular polymer Y includes a hydroxyl-containing monomer unit as a hydrophilic group-containing monomer unit, the hydroxyl-containing monomer unit in the granular polymer Y is preferably 0.5% by mass or more, more preferably 1% by mass or more, preferably 5% by mass or less, more preferably 2% by mass or less, and more preferably 1.5% by mass or less, when all monomer units contained in the granular polymer Y are taken as 100% by mass. If the acidic group-containing monomer unit in the granular polymer Y contains a ratio of more than the above lower limit, the softness of the electrode composite material layer formed can be further improved. On the other hand, if the acidic group-containing monomer unit in the granular polymer Y contains a ratio of less than the above upper limit, the dispersibility of the slurry composition and the adhesion of the electrode composite material layer formed can be fully and highly ensured.
[0198] <<Type of granular polymer Y>>
[0199] Moreover, as the particulate polymer Y containing a hydrophilic group, it is preferred to use, for example, an acrylic polymer containing a hydrophilic group or a conjugated diene polymer containing a hydrophilic group. From the viewpoint of ensuring sufficiently high cycle characteristics of the secondary battery, it is more preferred to use an acrylic polymer containing a hydrophilic group.
[0200] -Acrylic polymer containing hydrophilic group-
[0201] The acrylic polymer containing hydrophilic groups is a copolymer that contains at least (meth) acrylate monomer units in addition to the above-mentioned hydrophilic group-containing monomer units. In addition, the acrylic polymer containing hydrophilic groups preferably also contains nitrile-containing monomer units or aromatic vinyl monomer units. In addition, the acrylic polymer containing hydrophilic groups can also contain monomer units other than the hydrophilic group-containing monomer units, (meth) acrylate monomer units, nitrile-containing monomer units and aromatic vinyl monomer units.
[0202] The content ratio of the hydrophilic group-containing monomeric unit in the hydrophilic group-containing acrylic polymer can be in the same range as the preferred range of the content ratio of the hydrophilic group-containing monomeric unit in the above-mentioned polymer.
[0203] As the (meth)acrylate monomer that can form the (meth)acrylate monomer unit in the hydrophilic group-containing acrylic polymer, alkyl (meth)acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl acrylate can be used. In addition, these can be used alone or in any ratio.
[0204] In addition, in this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0205] Here, the content ratio of the (meth) acrylate monomer unit in the acrylic polymer containing a hydrophilic group is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and more preferably 80% by mass or less, when all monomer units contained in the acrylic polymer containing a hydrophilic group are taken as 100% by mass. If the content ratio of the (meth) acrylate monomer unit in the acrylic polymer containing a hydrophilic group is within the above-defined range, the adhesion and flexibility of the formed electrode composite material layer can be further improved.
[0206] As the nitrile group-containing monomer capable of forming the nitrile group-containing monomer unit in the hydrophilic group-containing acrylic polymer, the nitrile group-containing monomer capable of forming the above-mentioned polymer X can be used.
[0207] The proportion of the nitrile-containing monomeric unit in the acrylic polymer containing a hydrophilic group is preferably 5% by mass or more, more preferably 10% by mass or more, more preferably 17% by mass or more, preferably 40% by mass or less, more preferably 35% by mass or less, and more preferably 26% by mass or less, when all monomeric units contained in the acrylic polymer containing a hydrophilic group are taken as 100% by mass. If the proportion of the nitrile-containing monomeric unit in the acrylic polymer containing a hydrophilic group is within the above-mentioned prescribed range, the adhesion and flexibility of the electrode composite material layer formed can be further improved.
[0208] As the aromatic vinyl monomer capable of forming the aromatic vinyl monomer unit in the hydrophilic group-containing acrylic polymer, the aromatic vinyl monomers described in the section of “hydrophilic group-containing conjugated diene polymer” described later can be used.
[0209] The content ratio of the aromatic vinyl monomer unit in the hydrophilic group-containing acrylic polymer is preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 17 mass % or more, and is preferably 40 mass % or less, more preferably 35 mass % or less, further preferably 25 mass % or less, when all the monomer units contained in the hydrophilic group-containing acrylic polymer are taken as 100 mass %.
[0210] -Conjugated diene polymer containing hydrophilic group-
[0211] The hydrophilic group-containing conjugated diene polymer is a copolymer containing a conjugated diene monomer unit in addition to the above-mentioned hydrophilic group-containing monomer unit.
[0212] As specific examples of conjugated diene polymers, there are no particular limitations, and examples include: copolymers containing hydrophilic group-containing styrene-butadiene copolymers (containing hydrophilic groups SBR) and the like, containing hydrophilic group-containing monomer units, aromatic vinyl monomer units and aliphatic conjugated diene monomer units; butadiene rubber containing hydrophilic groups (containing hydrophilic groups BR) (combining copolymers containing hydrophilic group-containing monomer units and butadiene units); acrylic rubber containing hydrophilic groups (containing hydrophilic groups NBR) (combining copolymers containing hydrophilic group-containing monomer units, acrylonitrile units and butadiene units); and their hydrogenated products, etc. These can be used alone or in any ratio.
[0213] Among them, from the viewpoint of further improving the adhesion and flexibility of the formed electrode composite material layer, it is preferred to use a copolymer containing a hydrophilic group-containing monomer unit, an aromatic vinyl monomer unit and an aliphatic conjugated diene monomer unit, such as a hydrophilic group-containing styrene-butadiene copolymer (hydrophilic group-containing SBR).
[0214] The content ratio of the hydrophilic group-containing monomer unit in the hydrophilic group-containing conjugated diene polymer can be in the same range as the preferred range of the content ratio of the hydrophilic group-containing monomer unit in the above-mentioned polymer.
[0215] As the conjugated diene monomer unit that can form the conjugated diene monomer unit in the conjugated diene polymer containing a hydrophilic group, conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene can be cited. These can be used alone or in any ratio. 1,3-butadiene is particularly preferred.
[0216] The content ratio of the conjugated diene monomer unit in the conjugated diene polymer containing a hydrophilic group is preferably 15% by mass or more, more preferably 20% by mass or more, more preferably 25% by mass or more, preferably 60% by mass or less, more preferably 50% by mass or less, and more preferably 40% by mass or less, when all monomer units contained in the conjugated diene polymer containing a hydrophilic group are taken as 100% by mass. If the content ratio of the conjugated diene monomer unit in the conjugated diene polymer containing a hydrophilic group is within the above-mentioned prescribed range, the adhesion and flexibility of the electrode composite material layer formed can be further improved.
[0217] As aromatic vinyl monomers capable of forming aromatic vinyl monomer units in the conjugated diene polymer containing a hydrophilic group, styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. can be mentioned. These can be used alone or in any ratio. Styrene is particularly preferred.
[0218] The proportion of the aromatic vinyl monomer unit in the conjugated diene polymer containing a hydrophilic group is preferably 30% by mass or more, more preferably 45% by mass or more, more preferably 56% by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and more preferably 71% by mass or less, when all monomer units contained in the conjugated diene polymer containing a hydrophilic group are taken as 100% by mass. If the proportion of the aromatic vinyl monomer unit in the conjugated diene polymer containing a hydrophilic group is within the above-mentioned prescribed range, the adhesion and flexibility of the electrode composite material layer formed can be further improved.
[0219] <<Method for preparing granular polymer Y>>
[0220] The polymerization method of the particulate polymer A is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. may be used. In addition, as the polymerization reaction, addition polymerization such as ion polymerization, free radical polymerization, and living free radical polymerization may be used. Moreover, the emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. that can be used for the polymerization may be those commonly used, and the amount used may also be the amount commonly used.
[0221] <<Content ratio in slurry composition>>
[0222] The proportion of the particulate polymer Y in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, when the total solid content contained in the slurry composition is taken as 100% by mass, preferably 0.1% by mass and 5% by mass, more preferably 0.1% by mass and 3% by mass, more preferably 0.1% by mass and 2% by mass. If the proportion of the particulate polymer Y in the slurry composition is above the above lower limit, the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite material layer can be further improved. On the other hand, if the proportion of the polymer Y in the slurry composition is below the above upper limit, the internal resistance of the secondary battery can be reduced.
[0223] <Conductive materials>
[0224] The conductive material is a component having the function of ensuring electrical contact between electrode active materials in the electrode composite material layer.
[0225] As the conductive material, it is preferred to use at least carbon nanotubes, and it is more preferred to use carbon nanotubes and a particulate conductive material in combination.
[0226] If at least carbon nanotubes are used as the conductive material, the internal resistance of the secondary battery can be reduced. Furthermore, if carbon nanotubes and a granular conductive material are used together as the conductive material, the internal resistance of the secondary battery can be reduced and the flexibility of the electrode composite material layer can be further improved.
[0227] In addition, as the conductive material, conductive materials other than carbon nanotubes and granular conductive materials (other conductive materials) may be used. As other conductive materials, for example, fibrous conductive materials other than carbon nanotubes may be used.
[0228] <<Carbon Nanotube>>
[0229] Carbon nanotubes can reduce the internal resistance of a secondary battery by forming a conductive path in the electrode composite material layer. In addition, the use of carbon nanotubes can improve the cycle characteristics and low-temperature characteristics of a secondary battery.
[0230] The carbon nanotubes are not particularly limited as long as they are carbon nanotubes (hereinafter sometimes referred to as "CNTs") that can achieve the desired effects of the present invention. As carbon nanotubes, single-walled (SW) carbon nanotubes and multi-walled (MW) carbon nanotubes can be cited according to the type of wall. In addition, the carbon nanotubes that can be used as conductive materials can be any of single-walled carbon nanotubes, multi-walled carbon nanotubes, or a combination thereof.
[0231] The average number of CNT walls is preferably 10 or less, more preferably 9 or less, further preferably 8 or less, further preferably 2 or less, and further preferably 1.5 or less. When the average number of CNT walls is below the upper limit, the cycle characteristics of the secondary battery can be further improved.
[0232] The lower limit of the average number of walls of CNT is not particularly limited, but is usually 1 or more.
[0233] The average diameter of CNT is preferably 0.5nm or more, more preferably 1nm or more, more preferably 1.5nm or more, more preferably 2nm or more, more preferably 2.5nm or more, preferably 20nm or less, more preferably 12nm or less, more preferably 8nm or less, more preferably 6nm or less, and more preferably 4nm or less. If the average diameter of CNT is above the lower limit, the agglomeration of CNT can be fully suppressed to fully ensure the dispersibility of CNT as a conductive material. On the other hand, if the average diameter of CNT is below the upper limit, a good conductive path can be formed in the electrode composite material layer to further reduce the internal resistance of the secondary battery, and the cycle characteristics of the secondary battery can be further improved.
[0234] The ratio of the G band peak intensity to the D band peak intensity in the Raman spectrum of CNT (G / D ratio) is preferably 0.6 or more, more preferably 1.2 or more, further preferably 2.1 or more, further preferably 3.0 or more, and further preferably 3.6 or more. If the G / D ratio of CNT is above the above lower limit, the cycle characteristics of the secondary battery can be further improved. In addition, the upper limit of the G / D ratio of CNT is not particularly limited, for example, 200 or less.
[0235] The BET specific surface area of CNT is preferably 100 m 2 / g or more, more preferably 200m 2 / g or more, more preferably 250m 2 / g or more, preferably 1200m2 / g or less, more preferably 1100m 2 / g or less, more preferably 1000m 2 When the BET specific surface area of CNT is within the above-specified range, the internal resistance of the secondary battery can be further reduced.
[0236] In the present invention, the "BET specific surface area" of CNT refers to the nitrogen adsorption specific surface area measured using the BET method.
[0237] [Method for producing carbon nanotubes]
[0238] The CNTs having the above-mentioned properties are not particularly limited, and can be produced using known methods such as an arc discharge method, a laser ablation method, and a super growth method.
[0239] [Content ratio in slurry composition]
[0240] The content ratio of CNT in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, when the total solid content contained in the slurry composition is taken as 100% by mass, it is preferably 0.01% by mass and 0.5% by mass. If the content ratio of CNT in the slurry composition is above the above lower limit, the internal resistance of the secondary battery can be further reduced. On the other hand, if the content ratio of CNT in the slurry composition is below the above upper limit, it is possible to ensure that the flexibility of the electrode composite material layer is sufficiently high.
[0241] <<Granular conductive material>>
[0242] The particulate conductive material is a component that can function as a conductive material in the electrode composite material layer and can improve the flexibility of the electrode composite material layer.
[0243] The granular conductive material is not particularly limited as long as it has a shape other than a fiber shape (e.g., a spherical shape, a plate shape, etc.), and examples thereof include carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.) and graphene, etc. In addition, these granular conductive materials may be used alone or in combination of two or more in any ratio.
[0244] [Content ratio in slurry composition]
[0245] The content ratio of the granular conductive material in the slurry composition can be appropriately adjusted within the range of the desired effect of the present invention, for example, when the total solid content contained in the slurry composition is taken as 100% by mass, it is preferably 0.1% by mass or more and 5% by mass or less. If the content ratio of the granular conductive material in the slurry composition is above the above lower limit, the flexibility of the electrode composite material layer can be further improved. On the other hand, if the content ratio of the granular conductive material in the slurry composition is below the above upper limit, the adhesion of the electrode composite material layer can be fully and highly ensured.
[0246] <<Mixing ratio of CNT and granular conductive material>>
[0247] The mixing ratio of CNT and granular conductive material is not particularly limited. For example, the proportion of the content of CNT in the slurry composition in the total content of CNT and granular conductive material is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, and more preferably 10% by mass or less. If the proportion of the content of CNT in the total content of CNT and granular conductive material is above the above lower limit, the internal resistance of the secondary battery can be further reduced. On the other hand, if the proportion of the content of CNT in the total content of CNT and granular conductive material is below the above upper limit, the flexibility of the electrode composite material layer can be further improved.
[0248] <Dispersion medium>
[0249] The slurry composition of the present invention generally contains a dispersion medium such as water.
[0250] In addition, as at least a part of the dispersion medium of the slurry composition of the present invention, for example, a solvent such as water contained in the binder composition used for preparing the slurry composition can be used.
[0251] <Other ingredients>
[0252] Furthermore, the slurry composition of the present invention may contain other components in addition to the above components. As other components, for example, the same components as those that can be contained in the above-mentioned adhesive composition can be used.
[0253] Furthermore, the slurry composition of the present invention may further include a dispersant as another component. As the dispersant, carboxymethyl cellulose and its salts; aromatic sulfonic acid formaldehyde condensates such as β-naphthalenesulfonic acid formaldehyde condensates and their salts, etc. can be used. Among them, from the viewpoint of further improving the adhesion of the electrode composite material layer, aromatic sulfonic acid formaldehyde condensates and their salts are preferably used, and β-naphthalenesulfonic acid formaldehyde condensate sodium salt is more preferably used.
[0254] When an aromatic sulfonic acid formaldehyde condensate or a salt thereof is used as a dispersant, the content of the aromatic sulfonic acid formaldehyde condensate or a salt thereof in the slurry composition can be, for example, 0.01% by mass or more and 0.5% by mass or less, based on 100% by mass of the total solid content contained in the slurry composition.
[0255] <Method for preparing slurry composition>
[0256] The slurry composition of the present invention is not particularly limited, and can be prepared, for example, by dispersing or dissolving the above-mentioned components in a dispersion medium. Specifically, the slurry composition can be prepared by mixing the above-mentioned components with a dispersion medium using a ball mill, a sand mill, a bead mill, a pigment disperser, an attritor, an ultrasonic disperser, a homogenizer, a planetary mixer, a FILMIX or other mixer.
[0257] Here, water is generally used as the dispersion medium, but an aqueous solution of an arbitrary compound, a mixed solution of a small amount of an organic medium and water, or the like may be used.
[0258] In addition, when preparing the slurry composition of the present invention, when using a conductive material such as the above-mentioned CNT and granular conductive material, it is also possible to prepare a dispersion in advance in which the conductive material such as the CNT and granular conductive material is dispersed in a dispersion medium such as water, and then mix the obtained dispersion with other components such as the electrode active material, the polymer X and the granular polymer Y.
[0259] (Electrode for non-aqueous secondary batteries)
[0260] The electrode of the present invention has an electrode composite material layer formed using the slurry composition of the present invention, and generally has a structure in which an electrode composite material layer is formed on a current collector. Therefore, the electrode composite material layer contains at least an electrode active material and a polymer X, and optionally also contains a particulate polymer Y and a conductive material, etc.
[0261] The components contained in the electrode composite material layer, such as the electrode active material, polymer X, particulate polymer Y and conductive material, are the components contained in the above-mentioned slurry composition, and the preferred content ratio of each component is the same as the preferred content ratio of each component when the total solid content contained in the slurry composition is taken as 100% by mass.
[0262] The preferred ratio of CNT content to the total content of CNT and particulate conductive material that can be contained in the electrode composite material layer is also the same as the preferred ratio of CNT content to the total content of CNT and particulate conductive material that can be contained in the slurry composition.
[0263] In addition, the electrode of the present invention may further include a conductive adhesive layer containing at least a conductive material and a binder between the current collector and the electrode composite material layer.
[0264] Furthermore, since the electrode composite material layer included in the electrode of the present invention is formed using the slurry composition of the present invention, it can exhibit excellent adhesiveness and flexibility.
[0265] In addition, the electrode composite material layer possessed by the electrode of the present invention is formed using the slurry composition of the present invention with excellent dispersibility, so it has a uniform structure. Furthermore, as described above, the flexibility of the electrode composite material layer possessed by the electrode of the present invention is also excellent, so when, for example, a secondary battery is manufactured, the electrode is wound, folded, etc. according to the shape of the secondary battery, and the generation of cracks can be suppressed. Therefore, the electrode of the present invention has an electrode composite material layer with a uniform structure and few cracks, so the internal resistance of the secondary battery can be reduced.
[0266] <Current collector>
[0267] As the current collector, a material having electrical conductivity and electrochemical durability can be used. Specifically, as the current collector, a current collector composed of metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. In addition, these materials can be used alone or in combination of two or more in any ratio.
[0268] When manufacturing an electrode further including the conductive adhesive layer between the electrode composite material layer and the current collector, for example, a current collector with a conductive adhesive layer formed on a current collector substrate can be used as the current collector.
[0269] As the current collector substrate, for example, a current collector made of the above-mentioned metal material can be used.
[0270] The method for forming the conductive adhesive layer on the current collector substrate is not particularly limited. For example, a slurry composition (also referred to as "conductive adhesive") in which a conductive material and an adhesive are at least dispersed or dissolved in a dispersion medium or solvent such as water, and a dispersant is further dispersed or dissolved is applied to the current collector substrate and then dried, thereby forming a conductive adhesive layer.
[0271] The conductive material is not particularly limited, and for example, the conductive material that can be contained in the above-mentioned slurry composition can be used. In addition, as the binder, it is not particularly limited, and the granular polymer Y that can be contained in the above-mentioned slurry composition can be used. Furthermore, as the dispersant, it is not particularly limited, and for example, known dispersants such as carboxymethyl cellulose and its salts can be used.
[0272] The method of applying the conductive adhesive to the current collector substrate and the method of drying the applied conductive adhesive are not particularly limited, and known methods can be used.
[0273] <Electrode composite material layer>
[0274] The electrode composite material layer is formed, for example, through the steps of: applying the slurry composition on the current collector (coating step); and drying the slurry composition applied on the current collector (drying step).
[0275] <<Coating process>>
[0276] As a method for applying the slurry composition on the current collector, it is not particularly limited, and a known method can be used. Specifically, as a coating method, a scraper method, an immersion method, a reverse roll coating method, a direct roll coating method, a gravure printing method, an extrusion method, a brush coating method, etc. can be used. At this time, the slurry composition can be applied only to a single side of the current collector, or it can be applied to both sides. In addition, the thickness of the slurry composition film on the current collector before drying after coating can be appropriately set according to the thickness of the electrode composite material layer obtained by drying.
[0277] <<Drying process>>
[0278] The method for drying the slurry composition applied on the current collector is not particularly limited, and a known method can be used, for example: a drying method using warm air, hot air, or low-humidity air; a vacuum drying method; a drying method using irradiation of infrared rays, electron beams, etc. By drying the slurry composition applied on the current collector in this way, an electrode composite material layer can be formed on the current collector, and an electrode having a current collector and an electrode composite material layer can be obtained.
[0279] In addition, after the drying step, the electrode composite material layer may be subjected to a press treatment using a die press or a roll press, etc. The press treatment can improve the peel strength of the electrode.
[0280] (Non-aqueous secondary battery)
[0281] The secondary battery of the present invention has the electrode of the present invention described above. For example, the secondary battery of the present invention has a positive electrode, a negative electrode, a separator and an electrolyte, and at least one of the positive electrode and the negative electrode is the electrode of the present invention described above. That is, the secondary battery of the present invention can have a positive electrode that is an electrode of the present invention and a known negative electrode as the negative electrode, or a negative electrode that is an electrode of the present invention and a known positive electrode as the positive electrode, or both the positive electrode and the negative electrode can be electrodes of the present invention. Moreover, in the positive electrode composite material layer, flexibility may be a problem in particular, so from the viewpoint of further improving the flexibility of the positive electrode composite material layer as an electrode composite material layer, the secondary battery of the present invention preferably has at least a positive electrode that is an electrode of the present invention.
[0282] Furthermore, the secondary battery of the present invention has the electrode of the present invention described above, and therefore has reduced internal resistance.
[0283] In addition, the following description will take a case where the nonaqueous secondary battery is a lithium ion secondary battery as an example, but the present invention is not limited to the following example.
[0284] <Positive electrode>
[0285] The positive electrode is not particularly limited, and may be the electrode of the present invention described above. That is, as the positive electrode, for example, a positive electrode having a positive electrode composite material layer formed from the slurry composition of the present invention and a current collector may be used.
[0286] When the electrode of the present invention is not used as the positive electrode, a known positive electrode can be used as the positive electrode.
[0287] <Negative electrode>
[0288] The negative electrode is not particularly limited and may be the electrode of the present invention described above. That is, as the negative electrode, for example, a negative electrode having a negative electrode composite material layer formed from the slurry composition of the present invention and a current collector may be used.
[0289] When the electrode of the present invention is not used as the negative electrode, a known negative electrode can be used as the negative electrode.
[0290] <Spacer>
[0291] As a separator, there is no particular limitation, and examples thereof include: microporous membranes using polyolefin resins (polyethylene, polypropylene, polybutene, polyvinyl chloride); microporous membranes using resins such as polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyamide-imide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene; woven or non-woven fabrics using polyolefin fibers; aggregates of particles composed of insulating materials, etc. Among these, microporous membranes using polyolefin resins (polyethylene, polypropylene, polybutene, polyvinyl chloride) are preferred from the perspective of being able to thin the overall thickness of the separator, thereby increasing the ratio of the electrode composite material layer in the secondary battery and increasing the capacity per unit volume.
[0292] <Electrolyte>
[0293] As the electrolytic solution, an electrolytic solution obtained by dissolving an electrolyte in a solvent can be used.
[0294] Here, as a solvent, an organic solvent that can dissolve the electrolyte can be used. Specifically, as a solvent, it is preferred to use: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. In addition, known additives such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), methyl ethyl sulfone, etc. can also be added to the solvent.
[0295] As an electrolyte, a lithium salt can be used. As a lithium salt, for example, a compound described in Japanese Patent Gazette No. 2012-204303 can be used. Among these lithium salts, LiPF6, LiClO4, and CF3SO3Li are preferred as electrolytes because they are easily dissolved in organic solvents and show a high degree of dissociation. In addition, one electrolyte can be used alone, or two or more electrolytes can be used in combination in any ratio. There is usually a tendency that the higher the degree of dissociation of the supporting electrolyte used, the higher the lithium ion conductivity. Therefore, the lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0296] Moreover, the secondary battery of the present invention is not particularly limited and can be manufactured using a known assembly method. Specifically, the secondary battery of the present invention can be manufactured, for example, by winding, folding, etc., the negative electrode, positive electrode and separator obtained above according to the battery shape as needed, placing them in a battery container, injecting electrolyte into the battery container and sealing, thereby manufacturing. Here, in order to prevent the rise of the internal pressure of the secondary battery, the occurrence of overcharge and discharge, etc., as needed, fuses, PTC elements and other anti-overcurrent elements, porous metal mesh, guide plates, etc. can also be provided. In addition, the shape of the secondary battery can be any one of, for example, coin-type, button-type, sheet-type, cylindrical, square, flat, etc.
[0297] In addition, the battery components such as the positive electrode, negative electrode and separator of the secondary battery are usually configured so that the positive electrode contacts one side of the separator and the negative electrode contacts the other side of the separator. More specifically, the positive electrode composite material layer contacts one side of the separator and the negative electrode composite material layer contacts the other side of the separator.
[0298] Example
[0299] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0300] Furthermore, unless otherwise specified, in a polymer obtained by polymerizing a plurality of monomers, the content ratio of a monomer unit formed by polymerization of a certain monomer in the polymer generally corresponds to the ratio (feed ratio) of the certain monomer in all monomers used in the polymerization.
[0301] In addition, various measurements and evaluations were performed according to the following methods.
[0302] <Weight average molecular weight and molecular weight distribution>
[0303] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained polymer X were measured by gel permeation chromatography (GPC), and the molecular weight distribution (Mw / Mn) was calculated.
[0304] In addition, the eluent (0.1 M Tris buffer (pH 9, 0.1 M KCl)) was prepared as follows.
[0305] 1) Prepare 0.8 L of ultrapure water and dissolve 12.11 g of tris(hydroxymethyl)aminomethane and 7.46 g of potassium chloride.
[0306] 2) 0.1 M hydrochloric acid was added dropwise to adjust the pH to 9.
[0307] 3) After adjusting the pH, add ultrapure water to the volumetric flask until the liquid volume reaches 1 L.
[0308] The sample was prepared as follows.
[0309] First, polymer X was added to 5 mL of the eluent to give a solid content concentration of 0.05 wt%, and a stirring bar was added at 25°C and stirred at 300 rpm for 30 minutes using a magnetic stirrer. The obtained solution was filtered with a 0.45 μm membrane filter and the filtrate was used as a measurement sample.
[0310] The measurement conditions of GPC are as follows.
[0311] Apparatus: Agilent 1260 Infinity II HPLC (Agilent Technologies)
[0312] Chromatographic column: TSKgel GMPWXL 13μm 300mm×7.8mm
[0313] Eluent: 0.1M Tris buffer (pH 9, 0.1M KCl)
[0314] Flow rate: 0.7mL / min
[0315] Detector: 1260 Infinity II RI detector (Agilent Technologies)
[0316] Column temperature: 40°C
[0317] Injection volume: 200 μL
[0318] Molecular weight standard: Standard polyethylene oxide (PEO)
[0319] Sample concentration: 0.05 mass% (solid content concentration)
[0320] <Volume average particle size D50 of granular polymer Y>
[0321] For each granular polymer produced in the examples and comparative examples, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring apparatus (manufactured by Beckman Coulter, product name "LS-230") in an aqueous dispersion having a solid content concentration adjusted to 0.1% by mass, the particle size (μm) at which the cumulative volume calculated from the smaller diameter side becomes 50% was determined as the volume average particle size D50 of the granular polymer.
[0322] <Dispersibility of slurry compositions of all examples and comparative examples>
[0323] According to JIS Z8803:1991, a single cylindrical rotational viscometer (Brookfield B-type viscometer) was used to measure the viscosity of the positive electrode slurry composition at a rotation speed of 60 rpm and a temperature of 25°C, and it was confirmed to be within the range of 1000 mPa·s to 2000 mPa·s. According to the value of the solid content concentration of the positive electrode slurry composition with a viscosity within the above range, the dispersibility of the positive electrode slurry composition was evaluated according to the following criteria. In addition, in the same type of slurry composition, the larger the value of the solid content concentration in the same viscosity range (1000 mPa·s to 2000 mPa·s), the better the solid content contained in the slurry composition is dispersed, that is, the more excellent the dispersibility of the slurry composition.
[0324] A: Solid content concentration is 52% or more
[0325] B: Solid content concentration is 50% or more and less than 52%
[0326] C: Solid content concentration is 48% or more and less than 50%
[0327] D: Solid content concentration is less than 48% or not dispersed (no fluidity)
[0328] <Adhesion of the positive electrode material layers of all examples and comparative examples>
[0329] The positive electrode for lithium-ion secondary battery is cut into a rectangle of 1.0cm in width × 10cm in length as a test piece. After a transparent tape (transparent tape specified in JIS Z1522) is pasted on the surface of the positive electrode composite material layer side of the test piece, the stress when the transparent tape is peeled off from one end of the test piece at a speed of 50mm / minute in a 90° direction is measured. A total of three measurements are made, and the average value is obtained, which is used as the peel strength (N / m) and evaluated by the following benchmarks. The greater the peel strength, the better the adhesion of the positive electrode composite material layer, and the more firmly it fits with the current collector.
[0330] A + : Peel strength is 25N / m or more
[0331] A: Peel strength is 20N / m or more
[0332] B: Peel strength is 18 N / m or more and less than 20 N / m
[0333] C: Peel strength is 16 N / m or more and less than 18 N / m
[0334] D: Peel strength less than 16N / m
[0335] <Flexibility of the positive electrode material layer of all examples and comparative examples>
[0336] On the positive electrode composite material layer side of the positive electrode for lithium ion secondary battery, SUS cylindrical rods with different diameters ( and ), the positive electrode is wound on the cylindrical rod, and the positive electrode composite material layer is evaluated by visual observation whether it is broken. When the positive electrode is wound on the SUS cylindrical rod, the smaller the minimum diameter of the SUS cylindrical rod that the positive electrode composite material layer can keep without breaking, the more excellent the flexibility of the positive electrode composite material layer is.
[0337] A: and The cylindrical rods are not broken.
[0338] B: In The cylindrical rod is broken, but and The cylindrical rod does not crack
[0339] C: and The cylindrical rod is broken, but The cylindrical rod does not crack
[0340] D: In and The cylindrical rods are all broken
[0341] <Internal resistance of Example 1-1 to Comparative Example 1-5>
[0342] The lithium-ion secondary battery is charged to 50% of SOC (State Of Charge) at 1C (C is the value represented by the rated capacity (mA) / 1 hour (h)) at 25°C. Afterwards, at 25°C, charge for 20 seconds and discharge for 20 seconds at 0.2C, 0.5C, 1.0C, 2.0C, and 3.0C, respectively, with 50% of SOC as the center. The battery voltage after 20 seconds in each case (charging side and discharging side) is plotted against the current value, and its slope is calculated as the IV resistance (Ω) (IV resistance during charging and IV resistance during discharging). The value of the IV resistance (Ω) obtained is evaluated according to the following criteria. The smaller the value of the IV resistance, the smaller the internal resistance of the lithium-ion secondary battery.
[0343] A: IV resistance is less than 8Ω
[0344] B: IV resistance is 8Ω or more and less than 10Ω
[0345] C: IV resistance is 10Ω or more and less than 12Ω
[0346] D: IV resistance is 12Ω or more
[0347] <Output characteristics of Example 2-1 to Comparative Example 2-1>
[0348] After the lithium ion secondary batteries prepared in Example 2-1 to Comparative Example 2-1 were injected with electrolyte, they were left to stand at a temperature of 25°C for 5 hours. Next, they were charged to an SOC (State Of Charge) of 20% by a constant current method at a temperature of 25°C and 0.1C, and then aged at a temperature of 60°C for 12 hours. Then, they were discharged to a battery cell voltage of 2.6V by a constant current method at a temperature of 25°C and 0.2C. After that, CC-CV charging was performed at a constant current of 0.2C (upper limit battery cell voltage 3.6V), and CC discharge was performed at a constant current of 0.2C to a battery cell voltage of 2.6V. This 0.2C charge and discharge was repeated three times. The third discharge capacity of 0.2C was taken as the initial capacity CX. After that, CC-CV charging was performed at a constant current of 0.2C (upper limit battery cell voltage 3.6V), and CC discharge was performed at a constant current of 2.0C to a battery cell voltage of 2.6V, and the discharge capacity at this time was taken as CY. The 2.0C / 0.2C discharge capacity retention ratio represented by (CY / CX)×100(%) was determined and evaluated according to the following criteria: The larger the discharge capacity retention ratio, the better the output characteristics of the lithium ion secondary battery.
[0349] A: 2.0C / 0.2C discharge capacity retention rate is more than 60%
[0350] B: 2.0C / 0.2C discharge capacity retention rate is 55% or more and less than 60%
[0351] C: 2.0C / 0.2C discharge capacity retention rate is 50% or more and less than 55%
[0352] D: 2.0C / 0.2C discharge capacity retention rate is less than 50%
[0353] (Example 1-1)
[0354] <Preparation of Binder Composition (Aqueous Solution of Polymer X)>
[0355] 770 parts of ion exchange water were placed in a 10 L flask with a rubber stopper, the temperature was heated to 40° C., and the inside of the flask was replaced with nitrogen at a flow rate of 100 mL / min. Next, 8 parts of acrylic acid (solubility in water: 80 g / 100 mL) as an ethylenically unsaturated carboxylic acid monomer, 8 parts of 2-methoxyethyl acrylate (solubility in water: 11.6 g / 100 mL, glass transition temperature: −50° C.) as an unsaturated monomer A, 9 parts of 2-hydroxyethyl methacrylate (HEMA, solubility in water: 35 g / 100 mL) as a hydroxyl-containing methacrylate monomer, and 75 parts of 2-hydroxyethyl acrylate (β-HEA, solubility in water: 70 g / 100 mL) as a hydroxyl-containing acrylate monomer were mixed and injected into the flask using a syringe. Then, 3 parts of a 10.0% aqueous solution of sodium L-ascorbate as a polymerization accelerator were added by syringe, and 10 minutes later, 38 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. One hour after the reaction was initiated, the temperature was raised to 55°C to allow the polymerization reaction to proceed. Two hours later, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator were added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. Three hours later, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator were added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. After 4 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 5 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask by syringe. After 6 hours, a reaction terminator was added, and the flask was opened to the air to terminate the polymerization reaction. Thereafter, the pH of the product was adjusted to 8 using an 8% aqueous solution of lithium hydroxide to obtain an aqueous solution of polymer X as a binder composition.
[0356] In addition, the polymerization conversion rate of the monomers in the above-mentioned polymerization reaction is about 100%, and the composition of the obtained polymer X (the content ratio of each monomer unit) is the same as the ratio (feed ratio) of each monomer in the total monomers used for the polymerization of the polymer X. In addition, the obtained polymer X is water-soluble as defined in this specification.
[0357] <Preparation of granular polymer Y>
[0358] A hydrophilic group-containing acrylic polymer as the particulate polymer Y was prepared as follows.
[0359] Into a 1L flask (reaction container) with a rubber stopper and a stirrer, 90 parts of ion exchange water and 0.5 parts of sodium lauryl sulfate as an emulsifier were added, the gas phase was replaced with nitrogen, and after the temperature was raised to 60°C, 0.3 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion exchange water and added.
[0360] On the other hand, 30 parts of ion exchange water, 0.5 parts of sodium lauryl sulfate as an emulsifier, 76 parts of 2-ethylhexyl acrylate as a (meth) acrylate monomer, 2.0 parts of itaconic acid as a carboxylic acid group-containing monomer, 1.0 parts of 2-hydroxyethyl acrylate (β-HEA) as a hydroxyl group-containing monomer, and 21 parts of acrylonitrile as a nitrile group-containing monomer were mixed in another container (emulsion container) to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned 1L flask with a rubber stopper over 3 hours to perform polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, it was further stirred at 80°C for 2 hours.
[0361] A 5% sodium hydroxide aqueous solution was added to the aqueous dispersion containing the polymer obtained above, and the pH was adjusted to 8 to obtain an aqueous dispersion of a granular polymer Y (acrylic polymer containing a hydrophilic group). In addition, the obtained granular polymer Y was water-insoluble as defined in this specification. The volume average particle size of the granular polymer Y was measured as described above. As a result, the volume average particle size was 135 nm.
[0362] <Preparation of CNT dispersion>
[0363] 0.4 parts of carbon nanotubes (BET specific surface area: 250 m 2 / g), 0.6 parts (solid content conversion amount) of carboxymethyl cellulose ("DAICEL1220" manufactured by Daicel Corporation) and 99 parts of ion exchange water, then mixed at a peripheral speed of 8 m / s for 1 hour using a bead mill using zirconia beads with a diameter of 1 mm to prepare a CNT dispersion with a solid content concentration of 1 mass%.
[0364] <Preparation of acetylene black dispersion>
[0365] 4.4 parts of acetylene black as a conductive material, 0.6 parts (solid content conversion amount) of carboxymethyl cellulose ("DAICEL 1220" manufactured by Daicel Corporation), and 95 parts of ion-exchanged water were stirred using a disperser (3000 rpm, 60 minutes) to prepare an acetylene black dispersion having a solid content concentration of 5% by mass.
[0366] <Preparation of positive electrode slurry composition>
[0367] Add 95.6 parts of olivine lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as a positive electrode active material, 0.9 parts (equivalent amount of solid content) of an aqueous solution of polymer X as a binder composition, and ion exchange water, adjust the solid content concentration to 78%, and mix using a planetary mixer (60 rpm, 50 minutes).
[0368] Next, acetylene black dispersion is added in an amount of 1.9 parts of acetylene black, and mixed using a planetary mixer (60 rpm, 10 minutes). Next, CNT dispersion is added in an amount of 0.1 parts of carbon nanotubes, and mixed using a planetary mixer (60 rpm, 10 minutes). Finally, 1.5 parts (equivalent to the solid content) of an aqueous dispersion of particulate polymer Y is added, mixed using a planetary mixer (40 rpm, 10 minutes), and a positive electrode slurry composition is prepared. In addition, when preparing a positive electrode slurry composition, water is added to adjust the viscosity of the obtained positive electrode slurry composition (measured according to JIS Z8803: 1991 using a single cylindrical rotational viscometer (Brookfield B-type viscometer). Temperature: 25 ° C, rotation speed: 60 rpm) to a range of 1000 mPa s to 2000 mPa s.
[0369] The dispersibility of the obtained slurry composition for positive electrode was evaluated. The results are shown in Table 1.
[0370] <Preparation of current collector with conductive adhesive layer>
[0371] As the current collector used for producing the positive electrode, a current collector with a conductive adhesive layer produced by the following method was used.
[0372] 70 parts of conductive carbon (graphite / acetylene black = 70 / 30 (mass ratio)) and 8 parts of carboxymethyl cellulose as a dispersant ("DAICEL1220" manufactured by Daicel Corporation) were added, and after stirring at 3000 rpm for 60 minutes using a disperser, 22 parts of an aqueous dispersion of granular polymer Y in terms of solid content were added, and further stirred at 1500 rpm for 10 minutes using a disperser to prepare a conductive adhesive.
[0373] The conductive adhesive was applied to the aluminum foil as the current collector substrate by a roller at a molding speed of 20 m / min using a casting method, and dried at 80° C. to form a conductive adhesive layer with a thickness of 1 μm. Thus, a current collector with a conductive adhesive layer formed on the current collector substrate was obtained.
[0374] <Manufacturing of positive electrodes for lithium-ion secondary batteries>
[0375] Use a notch wheel coater to obtain a unit area weight of 22 mg / cm after drying. 2 The positive electrode slurry composition obtained as described above was applied to the conductive adhesive layer side of the current collector with a conductive adhesive layer, dried at 90°C for 20 minutes and further dried at 120°C for 20 minutes, and then heated at 60°C for 10 hours to obtain a positive electrode raw material. The positive electrode raw material was rolled using a roller press to produce a positive electrode raw material with a density of 2.5 g / cm 3 The positive electrode sheet composed of the positive electrode composite material layer, the conductive adhesive layer and the aluminum foil was cut into pieces with a width of 48.0 mm and a length of 47 cm to prepare a positive electrode for a lithium ion secondary battery.
[0376] The adhesiveness and flexibility of the positive electrode composite material layer were evaluated using the obtained positive electrode for lithium ion secondary battery.
[0377] <Manufacturing of negative electrodes for lithium-ion secondary batteries>
[0378] Into a 5 MPa pressure-resistant container equipped with a stirrer, 65 parts of styrene as an aromatic vinyl monomer, 35 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 2 parts of itaconic acid as an ethylenically unsaturated carboxylic acid monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion-exchanged water as a solvent, and 1 part of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 55° C. to initiate polymerization.
[0379] When the monomer consumption reaches 95.0%, the reaction is terminated by cooling. A 5% sodium hydroxide aqueous solution is added to the aqueous dispersion containing the polymer thus obtained to adjust the pH to 8. Thereafter, the unreacted monomers are removed by heating and reduced pressure distillation. Then, the mixture is cooled to below 30°C to obtain an aqueous dispersion of a granular polymer as a binder material for the negative electrode.
[0380] 48.75 parts of artificial graphite and 48.75 parts of natural graphite as negative electrode active materials, and 1 part (solid content equivalent) of carboxymethyl cellulose as a thickener were added to the planetary mixer. Furthermore, the solid content concentration was diluted to 60% using ion exchange water, and then kneaded at a speed of 45 rpm for 60 minutes. After that, 1.5 parts of an aqueous dispersion of a particulate polymer obtained as a binder for the negative electrode as described above was added in terms of solid content equivalent, and kneaded at a speed of 40 rpm for 40 minutes. Then, ion exchange water was added in such a way that the viscosity became 3000 ± 500 mPa·s (B-type viscometer, measured at 25°C and 60 rpm), thereby preparing a negative electrode slurry composition.
[0381] Use a notch wheel coater to coat at a rate of 10 ± 0.5 mg / cm 2 The negative electrode slurry composition was applied to the surface of a copper foil having a thickness of 15 μm as a current collector. The copper foil coated with the negative electrode slurry composition was then conveyed in an oven at a temperature of 80° C. for 2 minutes at a speed of 400 mm / min, and further conveyed in an oven at a temperature of 110° C. for 2 minutes, thereby drying the negative electrode slurry composition on the copper foil to obtain a negative electrode raw material having a negative electrode composite material layer formed on the current collector.
[0382] The negative electrode raw material was rolled by a roller press to produce a density of 1.6 g / cm 3 The sheet-shaped negative electrode composed of the negative electrode composite material layer and the copper foil was then cut into pieces with a width of 50.0 mm and a length of 52 cm to prepare a negative electrode for a lithium ion secondary battery.
[0383] <Manufacturing of lithium-ion secondary batteries>
[0384] The electrode composite material layers of the positive electrode and the negative electrode of the lithium ion secondary battery are made to face each other, and a spacer (microporous film made of polyethylene) with a thickness of 15 μm is placed between the two, and a core with a diameter of 20 mm is used for winding to obtain a wound body. Then, the obtained wound body is compressed from one direction at a speed of 10 mm / second until the thickness becomes 4.5 mm. In addition, the compressed wound body is elliptical when viewed from above, and the ratio of its major diameter to minor diameter (major diameter / minor diameter) is 7.7.
[0385] In addition, a LiPF6 solution with a concentration of 1.0 M (solvent: a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), containing an additive: 2 volume % (solvent ratio) of vinylene carbonate) was prepared as an electrolyte.
[0386] After that, the compressed winding body was stored in an aluminum laminated case together with 3.2g of electrolyte. Then, a nickel lead was connected to a predetermined position of the negative electrode for the secondary battery, and an aluminum lead was connected to a predetermined position of the positive electrode for the lithium-ion secondary battery, and the opening of the case was sealed by heat to obtain a lithium-ion secondary battery. The lithium-ion secondary battery was a bag-shaped battery with a width of 35mm, a height of 60mm, and a thickness of 5mm, and the nominal capacity of the battery was 700mAh.
[0387] The internal resistance of the obtained lithium ion secondary battery was evaluated. The results are shown in Table 1.
[0388] (Example 1-2)
[0389] The preparation of the granular polymer Y was carried out as follows. In addition, the preparation of the binder composition (aqueous solution of polymer X), the preparation of the granular polymer Y, the preparation of the CNT dispersion, the preparation of the acetylene black dispersion, the preparation of the positive electrode slurry composition, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary battery, the preparation of the negative electrode for lithium ion secondary battery and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1-1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0390] <Preparation of granular polymer Y>
[0391] A hydrophilic group-containing styrene-butadiene copolymer (hydrophilic group-containing SBR) as a particulate polymer Y was prepared as follows.
[0392] Into a 5 MPa pressure-resistant container equipped with a stirrer, 63 parts of styrene as an aromatic vinyl monomer, 34 parts of 1,3-butadiene as a conjugated diene monomer, 2 parts of itaconic acid as a carboxylic acid group-containing monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl group-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion-exchanged water as a solvent, and 1 part of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 55° C. to initiate polymerization.
[0393] When the monomer consumption reaches 95.0%, the reaction is terminated by cooling. A 5% sodium hydroxide aqueous solution is added to the aqueous dispersion containing the polymer thus obtained, and the pH is adjusted to 8. Thereafter, the unreacted monomers are removed by heating and reduced pressure distillation. Then, the mixture is cooled to below 30°C to obtain an aqueous dispersion of SBR containing a hydrophilic group as a granular polymer Y. In addition, the obtained granular polymer Y is non-water-soluble as defined in this specification. For the granular polymer, the volume average particle size is measured as described above. As a result, the volume average particle size is 150nm.
[0394] (Examples 1-3 to 1-9, Example 1-12, Comparative Examples 1-1 to 1-5)
[0395] When preparing polymer X as a binder composition, the type and / or amount of the added monomers are changed so that the composition (content ratio of each monomer unit) of the obtained polymer X becomes as shown in Tables 1 to 3, respectively. In addition, the preparation of the binder composition (aqueous solution of polymer X), the preparation of the granular polymer Y, the preparation of the CNT dispersion, the preparation of the acetylene black dispersion, the preparation of the positive electrode slurry composition, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary battery, the preparation of the negative electrode for lithium ion secondary battery and the preparation of lithium ion secondary battery are carried out in the same manner as in Example 1-1, and various measurements and evaluations are performed. The results are shown in Tables 1 to 3.
[0396] (Examples 1-10)
[0397] When preparing the positive electrode slurry composition, no CNT dispersion is added, and the amount of acetylene black dispersion is changed from 1.9 parts to 3.0 parts. In addition, the preparation of the binder composition (aqueous solution of polymer X), the preparation of the granular polymer Y, the preparation of the acetylene black dispersion, the preparation of the positive electrode slurry composition, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary batteries, the preparation of the negative electrode for lithium ion secondary batteries and the preparation of lithium ion secondary batteries are carried out in the same manner as in Example 1-1, and various measurements and evaluations are performed. The results are shown in Table 2.
[0398] (Example 1-11)
[0399] When preparing the positive electrode slurry composition, the addition amount of olivine-type lithium iron phosphate (LiFePO4) as the positive electrode active material was changed from 94.8 parts to 96.2 parts, and no acetylene black dispersion (equivalent to 1.9 parts of acetylene black) was added, and the addition amount of CNT dispersion was changed from 0.1 parts to 0.5 parts of carbon nanotubes. In addition, the preparation of the binder composition (aqueous solution of polymer X), the preparation of the granular polymer Y, the preparation of the CNT dispersion, the preparation of the positive electrode slurry composition, the preparation of the current collector with a conductive adhesive layer, the preparation of the positive electrode for lithium ion secondary batteries, the preparation of the negative electrode for lithium ion secondary batteries, and the preparation of lithium ion secondary batteries were carried out in the same manner as in Example 1-1, and various measurements and evaluations were performed. The results are shown in Table 2.
[0400] In addition, in Tables 1 to 3 shown below,
[0401] "LFP" stands for olivine lithium iron phosphate.
[0402] "AA" represents acrylic acid unit,
[0403] "AA2ME" means 2-methoxyethyl acrylate unit (2-methoxyethyl acrylate unit),
[0404] "EA" represents ethyl acrylate units,
[0405] "MA" represents methyl acrylate units,
[0406] "AN" stands for acrylonitrile unit,
[0407] "BA" represents n-butyl acrylate unit (butyl acrylate unit),
[0408] "β-HEA" means 2-hydroxyethyl acrylate unit,
[0409] "HEMA" means 2-hydroxyethyl methacrylate units,
[0410] "ACR" means acrylic polymer containing a hydrophilic group, "SBR" means styrene-butadiene copolymer containing a hydrophilic group, and "CNT" means carbon nanotube.
[0411] "AcB" stands for acetylene black.
[0412] [Table 1]
[0413]
[0414] [Table 2]
[0415]
[0416] [Table 3]
[0417]
[0418] <Synthesis of water-soluble polymer>
[0419] (Example 2-1)
[0420] The results are shown in Table 4. The same operations, measurements, and evaluations as in Example 1-1 were performed except that the polymer X, particulate polymer Y, and positive electrode slurry composition prepared as described below were used.
[0421] <Preparation of Binder Composition (Aqueous Solution of Polymer X)>
[0422] After adding ion exchange water and an 8% aqueous solution of sodium hydroxide to the acrylic acid monomer, neutralization was performed in a manner that the pH became 8.0 to prepare a sodium acrylate aqueous solution (solid content concentration: 3.0%). 680 parts of ion exchange water were added to a 10L flask with a rubber stopper, the temperature was heated to 55°C, and the flask was replaced with nitrogen at a flow rate of 100 mL / min. Next, 9.0 parts of sodium acrylate as an acidic group-containing monomer, 40.0 parts of 2-methoxyethyl acrylate as a monomer represented by formula (I) (a (meth)acrylate monomer not containing a hydroxyl group), 51.0 parts of 2-hydroxyethyl acrylate as a hydroxyl-containing (meth)acrylate monomer, and 0.2 parts of 1-thioglycerol as a chain transfer agent were mixed and injected into the flask with a syringe. Then, 3 parts of a 10.0% aqueous solution of sodium L-ascorbate as a polymerization accelerator were added by syringe, and 10 minutes later, 25 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. One hour after the reaction was initiated, the temperature was raised to 70°C to carry out polymerization reaction. Two hours later, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator were added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. Three hours later, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator were added by syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator were added to the flask by syringe. After 4 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added with a syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask with a syringe. After 5 hours, 0.5 parts of a 10.0% aqueous solution of sodium bisulfite as a polymerization accelerator was added with a syringe, and 10 minutes later, 5 parts of a 4.0% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask with a syringe. After 6 hours, a reaction terminator was added, and the flask was opened to the air to terminate the polymerization reaction. Thereafter, the pH of the product was adjusted to 8 using an 8% aqueous solution of sodium hydroxide, thereby obtaining a water-soluble polymer. For the obtained water-soluble polymer, the weight average molecular weight was measured as described above. The results are shown in Table 1.
[0423] The composition of the obtained water-soluble polymer is the same as the ratio (feed ratio) of each monomer in the total monomers used for polymerization of the water-soluble polymer. The obtained water-soluble polymer is water-soluble as defined in the present specification.
[0424] <Preparation of granular polymer Y>
[0425] A particulate polymer (hydrophilic group-containing acrylic polymer) as a binder material was prepared according to the following procedure.
[0426] Into a 1L flask (reaction container) with a rubber stopper and a stirrer, 90 parts of ion exchange water and 0.5 parts of sodium lauryl sulfate as an emulsifier were added, the gas phase was replaced with nitrogen, and after heating to 60°C, 0.3 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 20.0 parts of ion exchange water and added.
[0427] On the other hand, 30 parts of ion exchange water, 0.5 parts of sodium lauryl sulfate as an emulsifier, 78.0 parts of butyl acrylate, 2.5 parts of itaconic acid, 1.0 parts of 2-hydroxyethyl acrylate, and 18.5 parts of styrene were mixed in another container (emulsion container) to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned 1L flask with a rubber stopper over 3 hours to perform polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, it was further stirred at 80°C for 2 hours to obtain an aqueous dispersion of a granular polymer.
[0428] To the aqueous dispersion of the granular polymer thus obtained, an 8% aqueous sodium hydroxide solution was added to adjust the pH to 8, thereby obtaining an aqueous dispersion of the granular polymer. The granular polymer thus obtained was water-insoluble as defined in this specification. The volume average particle size of the granular polymer was measured as described above. As a result, the volume average particle size was 135 nm.
[0429] <Preparation of positive electrode slurry composition>
[0430] Use a planetary mixer to mix (15 rpm, 15 minutes) 95.6 parts of olivine lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as a positive electrode active material and 2.0 parts of acetylene black as a conductive aid. Then, add 0.9 parts (equivalent to the solid content) of an aqueous solution of polymer X as a binder composition and ion exchange water, adjust the solid content concentration to 78%, and mix using a planetary mixer (60 rpm, 50 minutes). Next, add water to adjust the viscosity of the slurry composition to a range of 3000 mPa·s to 4000 mPa·s. Furthermore, add 1.5 parts (equivalent to the solid content) of an aqueous dispersion of granular polymer Y, mix using a planetary mixer (40 rpm, 10 minutes), and prepare a slurry composition for the positive electrode. Finally, add water to adjust the viscosity of the slurry composition to a range of 1000 mPa·s to 2000 mPa·s. The dispersibility of the obtained positive electrode slurry composition was evaluated. The results are shown in Table 1. In addition, when preparing the positive electrode slurry composition, the viscosity of the obtained positive electrode slurry composition was measured using a single cylindrical rotational viscometer (Brookfield B type viscometer) in accordance with JIS Z8803:1991 (temperature: 25°C, rotation speed: 60 rpm).
[0431] (Example 2-2)
[0432] The results are shown in Table 4.
[0433] (Examples 2-3 to 2-10, 2-12, Comparative Example 2-1)
[0434] When preparing the polymer X as the adhesive composition, the type and / or amount of the added monomers were changed so that the composition (content ratio of each monomer unit) of the obtained polymer X was as shown in Tables 4 and 5, respectively. In addition, various operations, measurements and evaluations similar to those in Example 2-1 were performed. The results are shown in Tables 4 and 5.
[0435] (Example 2-11)
[0436] The slurry composition for positive electrode was prepared in the following manner, and the same operations, measurements and evaluations as those in Example 2-1 were performed except for the above. The results are shown in Tables 4 and 5.
[0437] <Preparation of CNT dispersion>
[0438] 0.4 parts of carbon nanotubes (BET specific surface area: 250 m 2 / g), 0.6 parts (solid content conversion amount) of carboxymethyl cellulose ("DAICEL1220" manufactured by Daicel Corporation) and 99 parts of ion exchange water, then mixed at a peripheral speed of 8 m / s for 1 hour using a bead mill using zirconia beads with a diameter of 1 mm to prepare a CNT dispersion with a solid content concentration of 1 mass%.
[0439] <Preparation of positive electrode slurry composition>
[0440] 95.6 parts of olivine lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as a positive electrode active material and 1.9 parts of acetylene black as a conductive aid were mixed using a planetary mixer (15 rpm, 15 minutes). Then, 0.9 parts (equivalent to the solid content) of an aqueous solution of polymer X as a binder composition and ion exchange water were added, the solid content concentration was adjusted to 78%, and mixed using a planetary mixer (60 rpm, 50 minutes). Next, the CNT dispersion was added in such a way that the amount of carbon nanotubes added was 0.1 parts, and mixed using a planetary mixer (60 rpm, 10 minutes). Next, water was added to adjust the viscosity of the slurry composition to within the range of 3000 mPa·s to 4000 mPa·s. Next, 1.5 parts (equivalent to the solid content) of an aqueous dispersion of granular polymer Y were added, mixed using a planetary mixer (40 rpm, 10 minutes), and a slurry composition for the positive electrode was prepared. Finally, water is added and adjusted so that the viscosity of the slurry composition is within the range of 1000 mPa·s to 2000 mPa·s.
[0441] The dispersibility of the obtained positive electrode slurry composition was evaluated. The results are shown in Table 1. In addition, when preparing the positive electrode slurry composition, the viscosity of the obtained positive electrode slurry composition was measured using a single cylindrical rotational viscometer (Brookfield B type viscometer) in accordance with JIS Z8803:1991 (temperature: 25°C, rotation speed: 60 rpm).
[0442] In addition, in Tables 4 and 5 shown below,
[0443] "LFP" stands for olivine lithium iron phosphate.
[0444] "AA" represents acrylic acid unit,
[0445] "AA2ME" means 2-methoxyethyl acrylate unit (2-methoxyethyl acrylate unit),
[0446] "EA" represents ethyl acrylate units,
[0447] "MA" represents methyl acrylate units,
[0448] "AN" stands for acrylonitrile unit,
[0449] "BA" represents n-butyl acrylate unit (butyl acrylate unit),
[0450] "β-HEA" means 2-hydroxyethyl acrylate unit,
[0451] "HEMA" means 2-hydroxyethyl methacrylate units,
[0452] "ACR" means an acrylic polymer containing a hydrophilic group, "SBR" means a styrene-butadiene copolymer containing a hydrophilic group, and "Aamid" means an acrylamide unit.
[0453] "HEAamid" means N-hydroxyethyl acrylamide units,
[0454] "CNT" stands for carbon nanotube,
[0455] "AcB" stands for acetylene black.
[0456] [Table 4]
[0457]
[0458] [Table 5]
[0459]
[0460] As can be seen from Tables 1 to 5, if the binder compositions of Examples 1-1 to 1-12 and Examples 2-1 to 2-12 containing polymer X are used, an electrode composite material layer with excellent flexibility can be formed, wherein the polymer X contains an acidic group-containing monomer unit and a repeating unit derived from an unsaturated monomer A whose solubility in water is within a specified range and whose glass transition temperature is below a specified value, and the content ratio of the acidic group-containing monomer unit and the content ratio of the repeating unit derived from the unsaturated monomer A of the polymer X are respectively within the specified range.
[0461] On the other hand, it is found that the flexibility of the electrode composite material layer is also poor when the binder compositions of Comparative Examples 1-1 and 2-1 containing a polymer in which the content ratio of the repeating unit derived from the unsaturated monomer A is out of the predetermined range are used.
[0462] Furthermore, when the binder compositions of Comparative Examples 1-2 to 1-3 containing polymers whose content ratio of acidic group-containing monomer units deviated from the predetermined range were used, the flexibility of the electrode composite material layer was also poor.
[0463] Furthermore, it is found that when the binder composition of Comparative Example 1-4 containing a polymer containing a repeating unit derived from an unsaturated monomer having a glass transition temperature exceeding a predetermined value instead of the repeating unit derived from the unsaturated monomer A is used, the flexibility of the electrode composite material layer is also poor.
[0464] Furthermore, it is found that when the binder composition of Comparative Example 1-5 containing a polymer containing a repeating unit derived from an unsaturated monomer whose solubility in water does not satisfy the prescribed range instead of the repeating unit derived from the unsaturated monomer A is used, the flexibility of the electrode composite material layer is also poor.
[0465] Industrial Applicability
[0466] According to the present invention, it is possible to provide a non-aqueous secondary battery electrode binder composition capable of allowing an electrode composite material layer to exhibit excellent flexibility.
[0467] Furthermore, according to the present invention, a slurry composition for non-aqueous secondary battery electrodes capable of allowing an electrode composite material layer to exhibit excellent flexibility can be provided.
[0468] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery electrode having an electrode composite material layer capable of exhibiting excellent flexibility.
[0469] Furthermore, according to the present invention, a nonaqueous secondary battery including the nonaqueous secondary battery electrode can be provided.
Claims
1. A binder composition for non-aqueous secondary battery electrodes, comprising a polymer X, The polymer X contains 3% by mass or more and 20% by mass or less of an acidic group-containing monomer unit, and 5% by mass or more and less than 50% by mass of a repeating unit derived from an unsaturated monomer A. The solubility of the unsaturated monomer A in water is 1 g / 100 mL or more and 15 g / 100 mL or less, The unsaturated monomer A has a glass transition temperature of 40° C. or less.
2. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein The polymer X contains 20% by mass or less of repeating units derived from the unsaturated monomer A.
3. The binder composition for non-aqueous secondary battery electrodes according to claim 2, wherein: The polymer X contains 55% by mass or more and 90% by mass or less of a hydroxyl group-containing acrylic acid ester monomer unit.
4. The binder composition for non-aqueous secondary battery electrodes according to claim 2, wherein: The weight average molecular weight of the polymer X is 50,000 or more and less than 500,000.
5. The binder composition for non-aqueous secondary battery electrodes according to claim 2, wherein: The polymer X contains 2% by mass or more and 30% by mass or less of a hydroxyl group-containing methacrylate monomer unit.
6. The binder composition for non-aqueous secondary battery electrodes according to claim 2, wherein: The unsaturated monomer A contains at least one selected from the group consisting of 2-methoxyethyl acrylate, ethyl acrylate, methyl acrylate and vinyl acetate.
7. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein The polymer X contains both or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate unit, and the total content ratio of the hydroxyl-containing acrylate monomer unit and the hydroxyl-containing methacrylate unit in the polymer X is 30 mass % or more and 90 mass % or less.
8. The binder composition for non-aqueous secondary battery electrodes according to claim 7, wherein: The polymer X comprises two or at least one of a hydroxyl-containing acrylate monomer unit and a hydroxyl-containing methacrylate monomer unit, In the polymer X, the total content of the repeating unit derived from the unsaturated monomer A, the hydroxyl group-containing acrylate monomer unit, and the hydroxyl group-containing methacrylate unit is 80% by mass or more.
9. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein The polymer X contains 3% by mass or more and 20% by mass or less of a (meth)acrylamide monomer unit. 10 . A slurry composition for non-aqueous secondary battery electrodes, comprising an electrode active material and the binder composition for non-aqueous secondary battery electrodes according to claim 1 .
11. The slurry composition for non-aqueous secondary battery electrodes according to claim 10, wherein The non-aqueous secondary battery electrode slurry composition further includes a particulate polymer Y containing a hydrophilic group.
12. The slurry composition for non-aqueous secondary battery electrodes according to claim 11, wherein The content of the particulate polymer Y is 0.1% by mass or more and 5% by mass or less, when the total solid content of the nonaqueous secondary battery electrode slurry composition is taken as 100% by mass.
13. The slurry composition for non-aqueous secondary battery electrodes according to claim 10, wherein The electrode active material contains olivine-type lithium iron phosphate.
14. The slurry composition for non-aqueous secondary battery electrodes according to claim 10, wherein The non-aqueous secondary battery electrode slurry composition further includes a conductive material containing carbon nanotubes.
15. The slurry composition for non-aqueous secondary battery electrodes according to claim 14, wherein The conductive material further comprises a granular conductive material. 16 . A non-aqueous secondary battery electrode, comprising an electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery electrode according to claim 10 . 17 . A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode according to claim 16 .
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Aqueous electrode binder for secondary battery
WO2012008539A1